Overcoming neoliberal globalization: social-ecological transformation from a Polanyian perspective and beyond - Brand, Ulrich; Görg, Christoph; Wissen, Markus (Globalizations, 2020)
The ecological crisis has intensified in many respects. Prominent proposals to deal with the crisis are discussed under the header 'sustainability transformations' or even 'Great Transformation'. We argue that most contributions suffer from a narrow analytical approach to transformation ignoring the largely unsustainable dynamics of global capitalism and the power relations involved in it. Thus, a 'new critical orthodoxy' of knowledge about transformation is emerging which runs the danger to contribute to a spatially and socially highly uneven green capitalism. This article claims that the current debate on social-ecological transformation can be enriched by a Polanyian understanding but also based on regulation theory. We distinguish between three types of transformation: incremental adaptation of the current institutional systems, institutional change in favour of a new 'green' phase of capitalism, and a post-capitalist great transformation that implies a profound structural change of the mode of production and living.
Political Science; Economics
Keywords: POLANYI; Karl; 1886-1964; capitalism; crises; debates & debating; ecological crisis; globalization; imperial mode of living; nature as fictitious commodity; regulation theory; social ecology; social-ecological transformation; sustainability

SEE Beyond Substantive Economics: Avoiding False Dichotomies - Spash, Clive L. (Ecological Economics, 2019)
The proposal has been put forward that ecological economics seek to become substantive economics (Gerber and Scheidel 2018). This raises important issues about the content and direction of ecological economics. The division of economics into either substantive or formal derives from the work of Karl Polanyi. In developing his ideas Polanyi employed a definition from Menger and combined this with Tönnies theory of historical evolution. In this paper I explore why the resulting substantive vs. formal dichotomy is problematic. In particular the article exposes the way in which trying to impose this dichotomy on history of economic thought and epistemology leads to further false dichotomies. Besides Polanyi, the positions of other important thinkers informing social ecological economics (SEE) are discussed including Neurath, Kapp and Georgescu-Roegen. The aim is to clarify the future direction of ecological economics and the role in that future of ideas raised under the topic of substantive economics.
Economics; Political Science
Keywords: economic anthropology; epistemology; formal economics; history of thought; social ecological economics; substantive economics

The Rise of Populist Movements in Europe: A Response to European Ordoliberalism? - Cayla, David (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
This article aims to explain the contemporary emergence of populism in the European Union. According to Polanyi's double movement framework, the emergence of these political forces can be understood as the result of protective responses from societies weakened by difficult market adjustments. Since the Single Act treaty (1986), the European economy took a path that intended to create a supranational self-adjusting markets economy based on the ordoliberal philosophy. However, by detaching the economic sphere from the reach of politics, the European Single Market has injured some important social institutions. The rise and the diversity of populisms in the European Union can therefore be explained by an attempt to preserve some national institutions that were diversely impacted by the market forces.
Economics; Political Science
Keywords: European Single Market; free enterprise; institutional economics; international relations; neoliberalism; ordoliberalism; populism; social functions; social institutions

Remittances and Households in the Age of Neoliberal Uncertainty - Khanal, Kalpana; Todorova, Zdravka (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
International migration and remittance flows have been reframed as catalysts for poverty reduction and development through marketization. Growth, measurement, and promotion of global remittances have emerged against the backdrop of neoliberal structural adjustment programs and financialization. Those processes have paralleled the emergence of the transnational household as a global institution. The article suggests that transnational households characterize a new stage of neoliberal capitalist development. The article revisits Karl Polanyi's The Great Transformation and discusses how active governance and neoliberal discourse regulate and frame labor and remittances as "fictitious commodities." Further, it is argued that transnational households take active roles in Polanyi's "double movement," by providing social protection amidst narrow public responsibility for provisioning. The article identifies this as a new element of "the great transformation," and referring to J. K. Galbraith, as a new age of neoliberal uncertainty.
Economics
Keywords: double movement; economic development; fictitious commodities; income; neoconservatism; neoliberalism; remittances; transnational households

The Double Movement Ten Years After the Fall of Lehman Brothers - Vidal, Gregorio; Marshall, Wesley C. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Ten years after the collapse of Lehman Brothers and the sharpest moments of panic within the global—and particularly the United States banking system—a somewhat strange dynamic has appeared. While the principal agents behind the crisis have collapsed their own institutions, the markets that they dominated, and even provoked what has been called the third crisis of economic theory, their political power has not waned. This theme has been well addressed by some academics such as Philip Mirowski (2013), while it has flummoxed others. In this article, we will argue that Karl Polanyi's theory of the "double movement" offers a coherent framework that is able to account for the history of the last ten years. Polanyi argues that different groups and members of society seek protection from the market, and that this search for protection has been the driving force between historical change. Polanyi does not ignore class; rather, he argues that different social classes can protect themselves in more or less effective ways. We argue that during the last ten years, the interests of globalized financial capital have been able to protect themselves with utmost effectiveness, while all other classes have been trammeled, often not even recognizing how or why actions are taken against the general interest.
Economics; History
Keywords: Lehman Brothers; capital market; double movement; financial crisis; financial markets; securities; stock exchanges; stocks (finance)

The Last Gasp of Neoliberalism - Watkins, John P.; Seidelman, James E. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
The ideas of both Thorstein Veblen and Karl Polanyi shed light on understanding the last gasp of neoliberalism. The last gasp refers to Donald Trump's abandonment of free trade, long considered a cornerstone of the neoliberal agenda, and his overt attacks on democratic institutions. In Trump, neoliberalism's attempt to overcome the gridlock of liberal democracy has revealed its fascist leanings. Both Polanyi and Veblen warned about the trend towards fascism. Trump was elected, in part, by filling the void left by the factioning of neoliberalism, in part by the injustice felt by people in rural areas, those with stagnant incomes, white males, and others. Trump has transcended the neoliberal agenda, approaching market relations from the point-of-view of the fight. The emergence of a predatory culture, in both the domestic and international realms, resembles the culture outlined in Veblen's The Theory of Business Enterprise. Trump's actions reveal the need to extend Polanyi's idea of social protection given the negative effects of modern technology and Trump's efforts to dismantle or reduce some regulatory agencies. Changing demographics and the adverse reaction to Trump's fascist leanings may yet see the emergence of a new progressive era, suggesting, at least, that Trump represents the last gasp of neoliberalism.
Economics
Keywords: POLANYI; Karl; 1886-1964; VEBLEN; Thorstein; 1857-1929; capitalism; democracy; double movement; fascism; international relations; neoliberalism

Financialization, Class Interests, and Karl Polanyi's Protective Response - Zalewski, David A. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Many observers expected a stronger countermovement against neoliberalism following the Great Recession. This article argues that such a protective response failed to materialize because the financialization process has aligned the preferences of labor and rentier classes. The result has been weaker support in democracies for expansionary monetary and fiscal policies during the early stages of recessions, which further lowers aggregate spending by increasing uncertainty. Thus, reversing the culture of financialization may be a necessary condition for preventing and responding to financial crises.
Business; Economics
Keywords: Polanyi; Karl; 1886-1964; business development; double movement; economic development; economic policy; financial crises; financialization; macroeconomic policy; monetary policy

Tensions in the Triangle: Monetary Plurality between Institutional Integration, Competition and Complementarity - Blanc, Jerome (Evolutionary and Institutional Economics Review, 2018)
This text aims at accounting for the plurality of money by emphasizing the delicate and evolving balance of the legal monetary systems and the continued existence of moneys that stay outside, though their continuation is subjected to chronic difficulties. It uses Polanyian concepts to take the wide and increasing variety of money into account and mobilizes criteria able to analyse the variety of links between them. It proposes a framework based on the representation of a "plurality triangle" with institutional integration, complementarity and competition, and it analyses the positioning of moneys in this framework as well as tensions that may generate shifts in their positioning.
Economics; Sociology
Keywords: current heterodox approaches: historical; evolutionary; institutional; monetary systems; money

Polanyi vs Hayek? - Mirowski, Philip (Globalizations, 2018)
Karl Polanyi and Friedrich Hayek are often portrayed as implacable intellectual opponents but their respective historical trajectories suggest some telling similarities. Here we describe some key similarities in their approach to markets, as a prelude to evaluating the political consequences of relying upon their Austrian conceptions of nature-based and constructivist framing of markets. Perhaps it is time to transcend their dichotomy.
Economics; Science and Technology Studies
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; POLANYI; Karl; 1886-1964; POLANYI; Michael; 1891-1976; constructivism; markets; science and technology; spontaneous order

Neoliberalism as a real utopia? Karl Polanyi and the theoretical practice of F. A. Hayek - Rodrigues, João (Globalizations, 2018)
This article interprets Hayek’s theoretical practice with the help of Polanyi’s framework. Hayek aimed at renewing liberalism after the interwar period, thus helping transforming it into neoliberalism, a real utopia instrumentally concerned with the political and moral economies underpinning markets. The distance between neoliberal theory and practice is less pronounced than it is sometimes assumed. The strength of neoliberalism partially stems from a capacity to articulate an effort to think about real-world mechanisms with an effort to demolish, reconfigure or transform existing structures. Despite his failure to anticipate neoliberalism, Polanyi gives ample intellectual resources to critically interpret the tasks that neoliberals would collectively have to face at the theoretical level, in an epoch of ideological marginality, before their triumphal political deployment at the global level.
Economics; Political Science
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; market; neoliberalism; utopia

The Moral Economists. R.H. Tawney, Karl Polanyi, E.P. Thompson, and the Critique of Capitalism - Gruber, Stephan (Economía (02544415), 2018)
Economics
Keywords: book review

Rethinking Money as an Institution of Capitalism and the Theory of Monetary Circulation: What Can Modern Heterodox Economists/Institutionalists Learn from Karl Polanyi? - Seccareccia, Mario; Correa, Eugenia (Journal of Economic Issues (Taylor & Francis Ltd), 2018)
Modern heterodox theories of money reject the neoclassical conception of money as primarily a medium to facilitate exchange. These heterodox theories of money all have as common starting point an analysis of credit-debt relations in which production is a central feature, with these economies organized along capitalistic design. The Keynesian-Marxian framework describing the process of monetary circulation, traditionally referred to as the theory of the monetary circuit (TMC), perhaps best represents this comprehensive vision. This broad TMC analytical framework is compatible with institutionalist theories of money that also point to the importance of credit-debt relations. The question, however, is whether this more unified heterodox theory of money, which describes sequentially monetary relations under capitalism, can be used to understand pre-capitalistic monetary institutions. By conceptualizing money as a means of payment rather than medium of exchange, Karl Polanyi’s analysis offers social scientists crucial insights to understanding monetary relations in all types of societies in which credit-debt relations have emerged historically.
Economics
Keywords: POLANYI; Karl; 1886-1964; credit; credit-debt relations; debt; heterodox economics; monetary circuit; money; money as a means of payment; neoclassical school of economics

La Contribución Del Análisis Institucional a Las Ciencias Sociales! - Polanyi, Karl (Revista de Economía Institucional, 2018)
El artículo presenta un discurso del autor en la Conferencia de la Sociedad de Postgrado de Economía de la Universidad de Colombia, Nueva York, en 1950, acerca del análisis institucional a las ciencias sociales. Comenta sobre la relación entre tales ramas de las ciencias sociales como la historia, la economía y la antropología. ENG: The article presents a speech by the author at the Conference of the Graduate Society of Economics of the University of Colombia, New York, in 1950, about the institutional analysis of the social sciences. Comment on the relationship between such branches of the social sciences such as history, economics and anthropology
History; Anthropology; Economics
Keywords: For a New West: Essays 1919-1958 (Book); POLANYI; Karl; 1886-1964; anthropology; anthropology & history; economics; ethnohistory; history & economics; original work; social science research; social sciences

Uncertainty, Control, and Karl Polanyi's Protective Response - Zalewski, David A. (Journal of Economic Issues, 2018)
Post-Keynesian institutionalist economists like Wallace Peterson and John Kenneth Galbraith recognized that the impact of uncertainty on economic wellbeing depends in part on the degree of control people have over the sources and consequences of it. Given the inability of government and other large institutions to reduce uncertainty or to provide citizens with the ability to manage it, mediating structures are considered as an alternative means of promoting economic security. The article concludes by describing and evaluating several of these alternatives.
Economics
Keywords: Austrian; Stockholm School; criteria for decision-making under risk and uncertainty; current heterodox approaches: historical; evolutionary; general welfare; history of economic thought since 1925: historical; history of economic thought: individuals; institutional; well-being

The Polanyian Intellectual Legacy for the 21st century: Recent Japan-based Research on the Contributions of Karl Polanyi - Midori Wakamori (Journal of Economics / Keizaigaku Zasshi, 2018)
This paper presents a memorial to the great Hungarian economist Karl Polanyi, with special emphasis on recent Japanese scholarship. To begin with, I affirm that for Polanyi “fictitious commodities” and “fictitious commodity markets" were key institutions of market society. Next I consider his assertion that the Poor Law controversy played a crucial role in introducing a competitive labor market into Britain from the second half of the 18th century to the first half of the 19th century. Polanyi explained that during that period a “theory of self-responsibility for poverty and unemployment” emerged, as did the beginning of economic liberalism. Then I emphasize that in his thinking, the rise of fascism is related to the fatal errors of liberal economic policymaking. According to Polanyi, the austerity policies of economic liberalism, which subordinated people's interests to those of the financial sector and undermined efforts to maintain peace, had a destructive influence on the lives of the people living in deficit states and in the Western democracies. His analysis of economic liberalism and fascism remains useful for considering the emergence of bad populism' (which is antithetical to democracy and human freedom) in our own age. Finally, in this paper, I examine Polanyi's thoughts on human freedom
Economics
Keywords: Japan; POLANYI; Karl; 1886-1964; Polanyian approaches; austerity (economics); labor market; labour market

Discursive Synergies for a ‘Great Transformation’ Towards Sustainability: Pragmatic Contributions to a Necessary Dialogue Between Human Development, Degrowth, and Buen Vivir - Beling, Adrián E.; Vanhulst, Julien; Demaria, Federico; Rabi, Violeta; Carballo, Ana E.; Pelenc, Jérôme (Ecological Economics, 2018)
There is a growing awareness that a whole-societal “Great Transformation” of Polanyian scale is needed to bring global developmental trajectories in line with ecological imperatives. The mainstream Sustainable Development discourse, however, insists in upholding the myth of compatibility of current growth-based trajectories with biophysical planetary boundaries. This article explores potentially fertile complementarities among trendy discourses challenging conventional notions of (un)sustainable development – Human Development, Degrowth, and Buen Vivir – and outlines pathways for their realization. Human Development presents relative transformative strengths in political terms, while Degrowth holds keys to unlocking unsustainable material-structural entrenchments of contemporary socio-economic arrangements, and Buen Vivir offers a space of cultural alterity and critique of the Euro-Atlantic cultural constellation. The weaknesses or blind spots (‘Achilles heels’) of each discourse can be compensated through the strengths of the other ones, creating a dialogical virtuous circle that would open pathways towards a global new “Great Transformation”. As one of the main existing platforms for pluralist and strong-sustainability discussions, Ecological Economics is in a privileged position to deliberately foster such strategic discursive dialogue. A pathway towards such dialogue is illuminated through a model identifying and articulating key discursive docking points.
Political Science; Sociology; Economics
Keywords: biophysics; degrowth; ecosystem services; environemntal economics; post-development; pragmatics; socio-ecological transition; strategic dialogue; sustainable development; transformation discourses

In Search of Substantive Economics: Comparing Today's Two Major Socio-metabolic Approaches to the Economy – MEFA and MuSIASEM - Gerber, Julien-François; Scheidel, Arnim (Ecological Economics, 2018)
Ecological economics is largely about the ‘substantive’ (in ‘kind’) study of the economy, as opposed to a purely ‘formal’ economic analysis (in ‘money’). Following Kapp, Polanyi and others, this article argues that ‘substantive economics’ is interested in the biophysical and politico-institutional structure of the economy rather than in correct prices within a particular axiomatic conformity, as in ‘formal economics’. After outlining the history of the substantive vs. formal dichotomy, we point out that socio-metabolic analyses are ecological economics' most significant contribution towards substantive economics. The core of this article then compares what could be today's two best candidates for offering a distinctive foundation to ecological economics as substantive economics: Material and Energy Flows Analyses (MEFA) and Multi-Scale Integrated Analyses of Societal and Ecosystem Metabolism (MuSIASEM). While MEFA is more easily comparative and historical, MuSIASEM is more integrative and comprehensive. Yet we also argue that socio-metabolic analyses represent one of the three pillars of substantive economics and that both MEFA and MuSIASEM are still weak in integrating the politico-institutional structure (second pillar) and a theory of needs (third pillar). If such an integration was done, ecological economics would be in a position to offer a full-fledge, alternative ‘substantive economic theory’.
Economics
Keywords: MEFA; MuSIASEM; biophysics; comparative studies; ecological economics; economic impact; environmental economics; social metabolism; substantive economics

Latin American Structuralism and Current Financialization - Déniz, José; Marshall, Wesley C. (International Journal of Political Economy, 2018)
In this article, we attempt to update the understanding of the external constraint in Latin America by examining the recent history of the region through the analytical framework of Karl Polanyi in The Great Transformation. As we argue, the greatest force behind today’s external restriction is the financial sector, much as it was a century ago. To reinforce this hypothesis, we provide the reader with relatively new historical material and with arguments made by scholars from diverse backgrounds. Taking into consideration the political and economic structures of Latin America, we argue that the international connections between the elite of the center and the periphery remain the key aspect in understanding today’s complex reality.
Development Studies; Economics
Keywords: Great Transformation; The (Book); Latin America; POLANYI; Karl; 1886-1964; external restriction; financialization; structuralism

Reconstructing Globalization in an Illiberal Era - DeMartino, George F. (Ethics & International Affairs, 2018)
In their new indictments of global neoliberalism and the economic profession's culpability in its harms, Dani Rodrik and Joseph Stiglitz press the case for reconstructed globalization that generates benefits for all and not just for corporate and financial elites. Both books are deeply consistent with the insights of Karl Polanyi, who had identified the inherent contradictions of the project to create what he called a self-regulating economy. Like Polanyi, Rodrik and Stiglitz are attentive to the inadequacies of neoliberalism, and both emphasize the capture of the state and international economic policy by elites, who have turned their backs on those left behind. While Stiglitz emphasizes that the profession knows how to fix the problem by applying modern Keynesian insights, Rodrik emphasizes the inherent epistemic limitations facing economists. Indeed, his arguments about development policy reflect the insights of Friedrich Hayek into the limits of economic expertise.
Economics; Political Science
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; RODRIK; Dani; STIGLITZ; Joseph; globalization; international relations; nationalism; neoliberalism; policy autonomy; trade; uncertainty

Capabilities Accumulation and Development: What History Tells the Theory - Dosi, Giovanni; Yu, Xiaodan (2018)
In this contribution we offer a broad overview of the technological, institutional and policy dynamics associated with the great transformation–borrowing Karl Polanyi (1944) expression–leading from traditional, mostly rural, economies to economies driven by industrial activities (and nowadays also advanced services), able to systematically learn how to implement and eventually how to generate new ways of producing and new products under conditions of dynamic increasing returns. Such a 'great transformation' entails a major process of accumulation of knowledge and capabilities, both at the levels of individuals and organizations. Certainly, part of such capabilities builds on education and formally acquired skills (what in the economists' jargon often goes under the heading of 'human capital'). However, at least equally important, capabilities have to do with the problem-solving knowledge embodied in organizations–concerning e.g. production technologies, the technical and social division of labor, labor relations as well as 'dynamic capabilities' of search and learning. In turn, the rates and directions of knowledge accumulation during the catch-up process and the ensuing effects upon the patterns of production and trade are shaped by the economic and institutional framework in which such processes are embedded.
Economics; Management Studies
Keywords: Great Transformation; The (Book); capability accumulation; catching-up; development; innovation

A ‘ordem natural’ de Smith e as visões críticas de Marx e Polanyi - Ferreira, Mateus Henrique Veloso (2018)
Esta monografia versa sobre as visões críticas de Karl Marx e Karl Polanyi à ideia de livre mercado proposta por Adam Smith. Smith disserta sobre a positividade no funcionamento automático dos mercados e, assim, funda o bem-estar das sociedades nas ações livres e espontâneas no domínio econômico. Marx crítica essa sociedade livre por visualizar grandes contradições em seu funcionamento, em especial no que diz respeito à relação de trabalho, uma vez que o trabalho é elemento fundamental na manutenção do sistema capitalista, mas ele ocorre de forma a alienar e explorar o trabalhador e, assim, impede o funcionamento positivo do próprio sistema a da vida do proletariado. Polanyi, por sua vez, critica o sistema de mercado por visualizar nele a capacidade negativa de sobrepor as relações econômicas às sociais, de modo que a humanidade e a natureza são convertidas em mercadorias, provocando, assim, a destruição do tecido social da sociedade.
Economics
Keywords: MARX; Karl; 1818-1883; SMITH; Adam; 1723-1790; livre mercado

Mercados, historia y teleología: reflexiones desde la noción de «doble movimiento» de Karl Polanyi - Polo Blanco, Jorge Polo (CONVIVIUM, 2018)
En el presente trabajo mostraremos que la filosofía liberal operó en muchas ocasionesa través de un esquema teleológico, desde el cual entendía que la espontaneidad delmovimiento histórico conducía de forma natural hacia una economía de mercados libres.Semejante interpretación tenía que presuponer otra controvertida tesis, a saber, que lascategorías que informan la racionalidad práctica dentro de una sociedad de mercado no sonuna simple contingencia histórica, sino que responden a la estructura lógica de cualquieracción humana; esto es, como si toda acción humana, en cualquier tiempo y lugar, hubiesefuncionado a través de una misma lógica inmutable que coincidía, en lo esencial, con laracionalidad típica de una economía de mercado. Para adentrarnos críticamente en estaproblemática utilizaremos la obra de Karl Polanyi, cuya obra se oponía frontalmente a estasdos tesis manejadas por el liberalismo económico.
Philosophy; Economics
Keywords: MISES; Ludwig von; doble movimiento; double movement; economía de mercado; historical teleology; market economy; teleología histórica

"Social Freedom" in the Twenty-First Century: Rereading Polanyi - Cangiani, Michele (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
Karl Polanyi's analysis of the genesis, crises, and institutional transformations of contemporary society is grounded on a theory of the basic features and dynamics of capitalism as a peculiar form of society. This article intends to develop this thesis on the basis of a reading of Polanyi's The Great Transformation, with references to Polanyi's preceding and later research. Polanyi's theoretical and methodological achievements suggest a wide comparative outlook and offer a critique of economics, in addition to being deeply connected with his political philosophy. Polanyi's approach seems to be nearer to the original institutional thought – from Karl Marx to Thorstein Veblen, from Max Weber to Adolf Löwe and Karl William Kapp – than to current neo-institutional tendencies in economics, sociology, and historiography. The hard problems society presently faces suggest the need to adhere to Polanyi's radical point of view – that is, to a radical approach to Polanyi's thought.
History; Economics
Keywords: Poor Law; WEBER; Max; 1864-1920; capitalism; comparative analysis; economic policy; economic systems; freedom in a complex society; institutional method; market society

Institutional Matrices Theory, or X- and Y-Theory: A Response to F. Gregory Hayden - Kirdina-Chandler, Svetlana (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
This article draws attention to issues about the institutional matrices theory (IMT) as perceived by and raised in the article by F. Gregory Hayden. To clarify the “controversial” points, I structure my response narrative along two lines. First, I present the prehistory of IMT, or X- and Y- theory, including earlier work by scientists related to the concept of institutional matrix. I connect the development of the actual IMT with the period of “perestroika” and the associated market experiments and reforms in Russia and Eastern European countries. One could see that the effects of market reforms in Russia were different in comparison with other countries in economic transition. I show that the institutional approach was accepted as more relevant to understanding the unexpected results in Russian society. I present IMT as a development of the ideas of Karl Polanyi and Douglas North to answer the challenges of explaining the real social and economic processes in Russia, as well as its wider application to a broader range of economic and social situations in different countries. Second, I then present the main IMT theses, giving special attention to the issues as perceived and raised by Hayden. In conclusion, I suggest the possibility of a joint project that combines IMT consideration and the social fabric matrix (SFM) concept of F. Gregory Hayden.
Economics
Keywords: HAYDEN; F. Gregory; Perestroika; Russia; economic policy; economics; institutional matrices theory; reciprocity

Food industry structure in Norway and Denmark since the 1990s: Path dependency and institutional trajectories in Nordic food markets - Klimek, Bjørn; Hansen, Henning Otte (Food Policy, 2017)
Structural changes in Norwegian and Danish food industry since the 1990s is analysed as a path dependent response to the neo-liberal turn. Norway entered the 1990s as a protected market and Denmark as case of an export oriented industry. These developmental strategies are rooted in early 20th century industrialisation and influenced by institutional transformations in the 1990s, such as EU and WTO. Mergers and acquisitions (M&A) are studied in the context of changing political environments. Explaining two different trajectories, we combine path dependency theories and a Polanyi inspired ‘varieties of capitalism’ framework with corporate strategy theories on food industry M&As. We identify two different types of path dependent development, a self-reinforcing in Denmark and a transformative ‘breaking point’ in Norway.
Economics
Keywords: Nordic food markets; World Trade Organization (WTO); agri-food chain; business planning; food economics; food industry - economic aspects; food industry structure; food marketing; food mergers and acquisitions (M&A); food policy; food supply management; institutional change; path dependency

Finance proud and industry vulnerable: When governments fail to defend the economic realm, citizens revolt - Pettifor, Ann (Juncture, 2017)
The subordination of society to self-regulating international markets is the reason why British workers and industries so often fall prey to predatory financiers, writes Ann Pettifor. It is also a fundamental cause of current political crises throughout the west – just as Karl Polanyi described almost 80 years ago.
Economics
Keywords: private equity firms; self-regulating market

Polanyi and Foucault on the Issue of Market in Classical Political Economy: Complementary Approaches to the Radical Theory of Social Control - Guizzo, Danielle; de Lima, Iara Vigo (Review of Radical Political Economics, 2017)
Studies have pointed out that the value of markets is related to their impact on the character of a society. Karl Polanyi's thesis about social disembeddedness attributed to 19th century economic liberalism the responsibility for consolidating the process of separating markets from society, which changed the dynamics between the state and population when economic rationality began dictating their connections. However, Polanyi only suggested analyses regarding power relations between these three elements and their effects on the social context. This paper argues that Michel Foucault's writings concerning technologies of power and biopolitics complement Polanyi's considerations insofar as they provide an understanding about how biopolitics emerged and how this led to a new posture of the state regarding population care and economic environment regulation.
Economics
Keywords: FOUCAULT; Michel; 1926-1984; biopolitics; classical economic liberalism; embeddedness; liberalism; political science; sociobiology; socioeconomic theory; socioeconomics

Karl Polanyi on economy and society: a critical analysis of core concepts - Hodgson, Geoffrey M. (Review of Social Economy, 2017)
The article presents the views of economic historian Karl Polanyi on the nature of economic and social embeddedness. Topics discussed include relationship between the economic and social embeddedness, the impact of the market economy, the transformation of society and production of material goods. Particular focus on limits of privatization, commodification, and marketization.
Economics
Keywords: business; capitalism; commodification; economic; economic activity; embeddedness; markets; social

Brexit and its Consequences - Pettifor, Ann (Globalizations, 2017)
In this brief essay, I argue that the ‘Brexit’ vote is but the latest manifestation of popular dissatisfaction with the utopian ideal of autonomous markets beyond the reach of regulatory democracy. Brexit represented the collective, if (to my mind) often misguided, efforts of those ‘left behind’ in Britain to protect themselves from the predatory nature of market fundamentalism. In a Polanyian sense, it is a form of social self-protection from self-regulating markets in money, trade and labour.
Economics
Keywords: BREXIT Referendum; 2016; Brexit; business; countermovement; democracy; double movement; financialization; markets; utopias

Aristóteles Descubre La Economía, Para Temerla. Una Lectura Desde Karl Polanyi - Polo Blanco, Jorge (ARISTOTLE DISCOVERS ECONOMY, TO FEAR IT. A READING THROUGH THE EYES OF KARL POLANYI., 2017)
This study approaches Aristotelian reflections on economy through the eyes of Karl Polanyi, as he resorts to the Greek philosopher to find useful elements when building a profound criticism of the modern market society. Aristotle intuited the uncertain future of a social order devoured by economic relations expanding at a hypertrophic rate. In his time, indeed, this was only a potential threat —he never saw the effective culmination of anything like what we are seeing today—. But he was nevertheless able to see the ultimate meaning of what was at stake, and to understand that the unmeasured, uncontrolled growth of market relations would irremediably affect civic balance. He understood that the unrestricted extension of the desire for profit to all human ties would be a powerful threat to the heart of the political community. (English)
Economics
Keywords: Aristotelian economic philosophy; ECONOMÍA DE LA ANTIGUA POLIS; FILOSOFÍA ECONÓMICA ARISTOTÉLICA; ancient capitalism; capitalismo antiguo; economic of ancient polis; market society; sociedad de mercado

Financialization and Society's Protective Response: Reconsidering Karl Polanyi's Double Movement - Watkins, John P. (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
Financialization challenges Karl Polanyi's thesis of double movement, the thesis that efforts to extend the market evoke efforts to protect humans, nature, and means of production from market forces. Financialization refers to the increased power of financial institutions. The government protects the incomes and assets of financial institutions, but it does little to protect the incomes and assets of households, which are necessary for people to afford healthcare, education, emergencies, retirement, and so on. Polanyi criticized nineteenthcentury civilization for transforming land, labor, and the means of production into commodities, using economic insecurity to motivate humans. The development of intangible property allowed business to expand the market in two ways: (i) restricting output to drive up profits and (ii) liquefying consumer assets to provide credit to consumers to increase spending. The implications of that process manifested themselves in the financial crisis of 2008. Market capitalism represented the attempt to organize commodities based on economic rationality. Similarly, the twentieth- and twenty-first-century capitalism represents the effort to "rationally" organize society according to the value of intangible assets. Both efforts failed, indicating the continued relevance of Polanyi's thesis.
Economics
Keywords: asset management; commons; double movement; financial services industry; financialization; global financial crisis; 2008-2009; intangible property; socioeconomic factors

What does karl polanyi offer to economic theory - Grdešić, M. (Ekonomski Pregled, 2017)
This article provides a critical overview of the theoretical perspective developed by Karl Polanyi, in particular his 1944 book The Great Transformation. What does this approach offer to economic theory, especially heterodox economic theory? Three elements vital to his work are in focus: (1) “embeddedness” of the market in society, (2) fictitious commodities (labor, nature and money) and (3) the “double movement”, i.e. the political imposition of the self-regulating market and the protective reaction of society. The springboard for this article is a survey of American economists, in which they were asked if they had read Polanyi’s work. © 2017, Hrvatsko Drustvo Ekonomista. All rights reserved.
Economics
Keywords: double movement; economic theory; embeddedness; fictitious commodities; heterodox economics

La « marchandisation » croissante du monde - Dupuis, Flavien (Esprit, 2016)
Un examen de la « marchandisation » montre qu’elle s’accompagne d’un processus inverse de dé-marchandisation, en particulier du travail, des ressources naturelles, du corps et des échanges, sous l’impulsion de l’État-Providence, du droit et de la société civile. ENG: "Commodification" is accompanied by the opposite movement of de-commodification, in particular for labor, natural ressources, bodies and exchanges, under the impulse of the Welfare state, law and civil society.
Economics
Keywords: commodification; decommodification

Polanyi, political-economic opportunity structure and protest: capitalism and contention in the post-communist Czech Republic - Císař, Ondřej; Navrátil, Jiří (Social Movement Studies, 2016)
Drawing on Polanyian logic, we focus on the gradual institutionalization of capitalism in the Czech Republic and the protests accompanying this process. We hypothesize that different configurations of political economy, or what we term the political economic opportunity structure, trigger different popular responses and are a potent indicator of expected protest forms. To analyze this we chose to carry out a country case study, in which many variables commonly associated with political mobilization, in particular the state’s institutional structure, are kept constant. By contrast, models of political economy vary over time, as a function of the extent and form of the international integration of capitalism. We focus on three configurations of political economy – national, globalized and austerity models – and for each one, identify the characteristics and mechanisms, i.e. concrete policy measures, that shape particular protest patterns in the context of our case study. In theoretical terms, this paper seeks to present one possible response, in this case a Polanyian response, to recent complaints about the disappearance of capitalism from social movement studies. At the same time, given the focus of this special issue, our goal is to analyze the current wave of anti-austerity protest that emerged in relation to what has been labelled the Great Recession.
Sociology; Economics
Keywords: Czech Republic; anti-austerity; economic protest; political economic opportunity structure; political opportunity structure; social movement studies

Formal Economy, Substantive Economy, and Economism - Sobel, Richard; Postel, Nicolas (Philosophy of the Social Sciences, 2016)
Polanyi analyzes the historical deployment of a “formal” economic science starting from the “market-scarcity-instrumental rationality triptych.” This triptych, and the knowledge associated with it, is shown to be more than merely a “substantial” economic science’s interest in the triptych “need-nature-institution.” While we must agree with Polanyi that economism is ill-suited to the first triptych, we hesitate to accept his suggested alternative, a heterogeneous mixture of naturalism and institutionalism, essentialism and historicism.
Sociology; Economics
Keywords: capital shortages; capitalism; economic systems; economism; essentialism (philosophy); formal economy; historicism; institutionalism (religion); profit; rationality; scarcity; substantive economy

TRANSNATIONAL GOVERNANCE REGIMES IN THE GLOBAL SOUTH: MULTINATIONALS, STATES AND NGOs AS POLITICAL ACTORS - Morgan, Glenn; Peinado Gomes, Marcus Vinícius; Perez-Aleman, Paola (Administração de Empresas em Revista, 2016)
The article discusses the function of the state within Polanyi's double movement and the limitations of the state as a governance mechanism under globalisation, the way transnational nongovernmental organizations (NGO) and social movements examine gaps in governance within capitalism as an alternative way of preventing the market powers exercised multinational corporation (MNC), and the way the Global South position itself within the global economy and the creation of governance mechanisms.
Economics
Keywords: double movement; globalization; nongovernmental organizations

Beyond prices: The cultural economy of water in the Cordillera highlands of Northern Luzon, Philippines - Abansi, Corazon L.; Doble, Maria Consuelo C.; Cariño, Jessica K.; Rola, Agnes C. (Asia Pacific Viewpoint, 2016)
This paper analyses how the economic actions of water distribution and exchange are embedded in the culture of indigenous communities in the Cordillera highlands of Northern Luzon, Philippines. Such actions are fundamental to water access and provisioning. Data was derived from a series of focus group discussions conducted with various water users, including households, farmers, enterprises and local government officials, and from upstream, midstream and downstream communities along the Balili River, a critical watershed in the Cordillera highlands. The study area exhibits a mix of livelihood systems and both formal and traditional institutions of decision-making. Recognising that water is both an economic and social good, this paper draws inspiration from Polanyi's concept of embeddedness. Cases of three communities suggest that water distribution and exchange are embedded in the community's socio-cultural spaces, but the extent of embeddedness declines as communities transform from subsistence to market-based economies. Embeddedness also determines value and availability of water. The paper contributes to the discourse on the cultural economy of water and provides direction on new modes of decision-making on river management that promise more inclusive, equitable and ecologically sustainable outcomes.
Economics
Keywords: Philippine Cordillera; cultural economy; embeddedness; water distribution and exchange

Neoliberalism, Polanyi's Protective Response, and Veblenian Waste - Wrenn, Mary V. (Journal of Economic Issues (Taylor & Francis Ltd), 2016)
As capitalism unfolds, continual technological advance – in combination with the relentless accumulation imperative – serves to amplify material progress. The expanding economic sphere begins to pervade the everyday lives and thinking of the individual. The institutionalization of the market fundamentally changes the structure of society and, in so doing, fundamentally changes the institutional structure through which individuals are socialized. The social dislocation generated therein prompts Karl Polanyi's protective response. Despite this market intensification, the existence of the economic surplus undermines the syllogistics of market-determined pricing. Evidence of the economic surplus and Veblenian waste as well as of the fact that the competitive law of value is not operable under neoliberalism is found in the lobby industry and campaign contributions. This research seeks to explicitly connect the concepts of Polanyi's protective response with Veblenian waste and the economic surplus in order to better understand how the irrational system of neoliberalism continues to evolve.
Sociology; Economics
Keywords: Veblen; capitalism; economic sociology; economic surplus; institutional economics; neoliberalism

Saving the Commons in an Age of Plunder - Batt, H. William (American Journal of Economics and Sociology, 2016)
Land ownership, as commonly understood today, originated with the enclosure movement during the English Tudor era almost four centuries ago. Karl Polanyi referred to this “propertization” of nature as the “great transformation.” That land, water, and air was a social commons is now archaic and forgotten, and with it the classical economic concept of rent, which was, in theory, once paid to royalty as the earth's guardian. Garrett Hardin's article, “The Tragedy of the Commons,” raised alarm about the abuse and loss of this realm, and he recommended constraints and privatization to prevent this. Most people view titles to landed property much as they do their household goods, but Henry George saw that the earth should be seen as a common resource and its value taxed to benefit everyone. This would restore economic equilibrium to market exchanges and pay for government services. The capture of natural resource rents can supplant taxes on wages and capital goods, and it comports with all textbook principles of sound tax theory. This policy can be the modern replacement for the commons, and implementing resource rent capture is both economically and technically feasible.
Economics; Sociology
Keywords: commons; propertization of nature

Towards Another 'Great Transformation' - Mkandawire, Thandika (Africa Insight, 2016)
As Karl Polanyi indicates in the 'Great Transformation',1'the so-called self-regulating markets cannot exist for any length of time without destroying human society'. Three 'Great Transformations' have taken place. The first occurred in Europe at a time when it was widely believed that markets were nature's way of managing exchange in an efficient way and that interference in the workings of the market, as Adam Smith argued, was not only artificial, but against the laws of God.2 The second was about society's reaction in defending itself against the ravages of the market. The third was when neoliberalism launched a counter-movement that gave the market primacy. This paper argues that the assumption that the self-regulation expected from 'corporate social responsibility', or the instinct for self-preservation, would replace the state, had failed disastrously. The neoliberal model is therefore in trouble. It is important to contemplate a new global order that will be built on and facilitate social orders that are developmental, socially inclusive and democratic - which will be the fourth 'Great Transformation'. As the paper argues, there are two imperatives: the first imperative would be the creation of global institutions that would ensure that commitments to justice, equality and democracy are translated into global and national policies; and the second one would be the intellectual and ideological challenge of the views and discursive practices that, all too often, fetishised globalisation into some exogenous force that ineluctably imposes its laws on the human race.
Economics; Development Studies
Keywords: Africa studies; Europe; democracy; economic conditions; humanism; justice administration; socioeconomics

Human growth and avoiding European disintegration: lessons from Polanyi - Buzaglo, Jorge (real-world economics review, 2016)
Many economists, including mainstream economists, have declared the necessity of an ambitious public investment program for Europe. The continuation of the present laissez-faire and austerity approach, they say, will deepen the dissatisfaction of European peoples with the European project. In effect, in the absence of inspiring progressive alternatives, there is the real prospect of nationalistic reactions everywhere, with fragmentation and the end of the EU (or even worse) as a consequence. At the bottom of EU-fatigue there is dissatisfaction with the present economic paradigm, which implies social and economic strain and stagnation for a large majority, and growing wealth and privilege for a tiny minority (the “one percent”). A new social and economic paradigm should be necessary to reverse the negative and dangerous trends that the now more than 30 years old neoliberal paradigm has implied. To be effective, a new social and economic paradigm should underlie the new, ambitious European investment program. The guiding general idea of such a new, hopeful paradigm and program should be the idea of human growth. Human growth can be understood as the growth of human capabilities — the all-round development of individuals and societies. The paper summarizes a dynamic simulation model for the efficient allocation of investment. Investment efficiency is understood in the sense of the intersectoral allocation of investments being able to fulfil desired patterns of capability growth. That is, efficient investment programs are those that maximize the capacity of the production system — and in general, the socioeconomic system — of generating human growth.
Economics
Keywords: European Union; human growth

Social Quality - Herrmann, Peter (International Journal of Social Quality, 2016)
A fundamental methodological problem is the relevance of an antagonism of capitalism. This needs to be classified in light of the developmental stage of the means of production: far too little attention is paid to the contradictory character of individualization and socialization. This brings us to Karl Polanyi's main argument of disembedding. He also deals with a shift from the socially integrated (and dependent) individual to the utilitarian market citizen. The French regulationist theory offers a major step toward understanding new forms of societal embedding linked to this "new personality." It will also allow us to move beyond the misleading juxtaposition or dichotomization of individualization-socialization. Investigating five major tensions, it ventilates the possible meaning of the digital revolution and the challenges for monitoring development. The main aim of the article, however, is to bring the economy back in and to go beyond the traditional duality between economics and politics.
Economics
Keywords: capitalism; change; development; disembedding; economics; economics and social science; economy & society; social quality; social sciences; theory of regulation; work

The Methodology of Polanyi's Great Transformation: Commentary - Mayhew, Anne (Economic Thought, World Economics Association, 2016)
A commentary on Asad Zaman's paper “The Methodology of Polanyi's Great Transformation”
Economics
Keywords: ZAMAN; Asad; capitalist systems; economic methodology; economic thought; history of economic thought; political economy

Distribution-Led Growth in the Long Run - Nikiforos, Michalis (Review of Keynesian Economics, 2016)
This paper examines the long-run fluctuations in growth and distribution through the prism of wage- and profit-led growth. It argues that the relation between distribution of income and growth changes over time and proposes an endogenous mechanism that leads to fluctuations between wage- and profit-led periods. The ephemeral character of distribution-led regimes needs to be taken into account when someone estimates empirically the effect of a change in distribution on utilization and growth. The model is a linear version of Goodwin's predator-prey model, but with a reversal of the roles for predator and prey; this is another way to conceptualize the symbiosis between the two classes within a capitalist economy. The aforementioned argument is also examined in relation to the double movement of Karl Polanyi and the inverse U-shaped curve proposed by Simon Kuznets.
Economics
Keywords: Kaleckian; Sraffian; aggregate factor income distribution; aggregate human capital; aggregate labor productivity; business fluctuations; capacity; capital; cycles; employment; general aggregative models: Marxian; intangible capital; intergenerational income distribution; investment; one; two; and multisector growth models; unemployment; wages

The Methodology of Polanyi's Great Transformation - Zaman, Asad (Economic Thought, 2016)
Polanyi's book, The Great Transformation, provides an analysis of the emergence and significance of capitalist economic structures which differs radically from those currently universally taught in economic textbooks. This analysis is based on a methodological approach which is also radically different from existing methodologies for economics, and more generally social science. This methodology is used by Polanyi without explicit articulation. Our goal in this article is to articulate the methodology used in this book to bring out the several dimensions on which it differs from current approaches to social science. Among the key differences Polanyi provides substantial scope for human agency and capability to change the course of history. He also shows that the social, political and economic spheres of human existence are deeply interlinked and cannot be analysed in isolation, as current approaches assume. KM - see Mayhew's (2016) commentary on this paper.
Economics
Keywords: capitalism; liberalism; methodology; social science

Sharing Economy: A Step towards the Re-embeddedness of the Economy? - Pais, Ivana; Provasi, Giancarlo (Stato e Mercato, 2015)
The expression "sharing economy" has spread exponentially in the past few years, a sign of the growing interest in a phenomenon that continues to maintain boundaries that are somewhat vague. The hypothesis of this paper is that this can be attributed not only to the pervasiveness and enabling power of new technologies but also to the need to fill a social vacuum due to the failures of the market and the state. The sharing economy is introducing collaborative social forms able (at least ideally) to embed economic relations within social ones. To test this hypothesis, the article uses the instrumentation implemented by Karl Polanyi to analyze the forms of integration of economy and society (exchange, reciprocity, redistribution). The political economy of the late twentieth century was especially interested in exchange (market) and redistribution (state), leaving social reciprocity in the background. However, we have to look at this more carefully to grasp any social and institutional innovation that the sharing economy can promote. The first part of this paper is devoted to an analysis of the forms of integration and, in particular, to reciprocity in its different variants. The second part, in light of the taxonomy proposed in the first, analyzes some of the most significant experiences of the sharing economy, seeking to determine the institutional characteristics and social dynamics that this could (at least potentially) engender and support. The conclusions will attempt to answer the questions formulated and indicate avenues for further research.
Economics; Sociology
Keywords: cooperative enterprises; economic anthropology; economic sociology; market structure; pricing; and design; open source products and markets; other economic systems: general; prices; public goods; reciprocity; renewable resources and conservation: demand and supply; sharing economy; social and economic stratification

The meta-crisis of secular capitalism - Milbank, John; Pabst, Adrian (International Review of Economics, 2015)
The current global economic crisis concerns the way in which contemporary capitalism has turned to financialisation as a double cure for both a falling rate of profit and a deficiency of demand. Although this turning is by no means unprecedented, policies of financialisation have depressed demand (in part as a result of the long-term stagnation of average wages) while at the same time not proving adequate to restore profits and growth. This paper argues that the current crisis is less the ‘normal’ one that has to do with a constitutive need to balance growth of abstract wealth with demand for concrete commodities. Rather, it marks a meta-crisis of capitalism that is to do with the difficulties of sustaining abstract growth as such. This meta-crisis is the tendency at once to abstract from the real economy of productive activities and to reduce everything to its bare materiality. By contrast with a market economy that binds material value to symbolic meaning, a capitalist economy tends to separate matter from symbol and reduce materiality to calculable numbers representing ‘wealth’. Such a conception of wealth rests on the aggregation of abstract numbers that cuts out all the relational goods and the ‘commons’ on which shared prosperity depends.
Economics
Keywords: abstraction; financialisation; financialization; materialisation; meta-crisis

Europe at a Crossroads: Failed Ideas, Fictional Facts, and Fatal Consequences - Thomasberger, Claus (Forum for Social Economics, 2015)
The crisis of the European Monetary Union has revealed the weakness and the fragility of the European integration process. The paper examines the institutional changes which are at the root of the instability. What are the driving forces behind the introduction of the euro? What role do theoretical considerations play in this process? What influence on European integration has been exerted by neoliberal beliefs and convictions? Relying on an approach that combines basic insights of Gunnar Myrdal with Karl Polanyi's idea of a "double movement," it concentrates on the institutional transformation that is at the basis of the European integration process. The relationship between (misleading) ideas and facts is at the center of the study. It examines the influence of ideas and theoretical models on European integration, the Single Market Program, the Maastricht process, the increasing imbalances since the introduction of the euro, and the strategies applied during the recent crisis.
Economics; Philosophy
Keywords: economic integration; financial aspects of economic integration; financial crises; international institutional arrangements

Hayek versus Polanyi: Espontaneidade e designio no capitalismo. (Hayek versus Polanyi: Spontaneity and Design in Capitalism. With English summary.) - de Almeida, Rafael Galvao; Garcia Fernandez, Ramon (Economica (Fluminense Federal University), 2015)
This work introduces the concept of spontaneous order, its development through many schools of economic thought and its importance to today's society. This paper gives emphasis to Friedrich Hayek, since he has the most known model of spontaneous order, how he started to elaborate from his research about the role of the information on the economy and his maturation in Law, Legislation and Liberty. As a counterpoint to the Hayekian model, this work includes criticism to the concept and the work of Karl Polanyi is analyzed. He diverged from Hayek about the role of the market in the society, when he affirmed that society protects itself from the invasion of the market in the other social spheres, through the process of double movement. Lastly, it is concluded that there is no evidence to discard the existence of spontaneous orders; the double, that double movement, because it is started with the individuals before taking legislative form, has the necessary characteristics to be considered a type of spontaneous order; and, due to the self-organizational trait of spontaneous order, there are practical problems in political anarchism.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; belief; communication; elections; history of economic thought; information and knowledge; learning; legislatures; lobbying; market structure; pricing; and design; political processes: rent-seeking; lobbying; elections; legislatures; and voting behavior; rent-seeking; spontaneous order; unawareness; voting behavior

Polanyi e Granovetter a partir do olhar de Lukacs. (Polanyi and Granovetter from Lukacs Glance. With English summary.) - de Araujo, Paulo Henrique Furtado (Economica (Fluminense Federal University), 2015)
The article critically examines the contributions of Polanyi and Granovetter on the embeddedness notions and functioning of any individual in social networks from the construction proposed by Lukacs in "The Ontology of Social Being". It is proposed to rethink and point clues to an explanation, consistent with the Marxian thought, the necessary links between the decision-making done in the here and now, in the quotidian of world of men, and the legalities and more general trends produced by them and felt by the entire social being.
Economics
Keywords: GRANOVETTER; Mark; LUKACS; Georg; Marxian; Sraffian; current heterodox approaches: socialist; economic anthropology; economic sociology; history of economic thought: individuals; language; social and economic stratification

Strengthening Karl Polanyi’s Concepts of Reciprocity, Double Movement, and Freedom with the Assistance of Abductive Logic - Hayden, F. Gregory (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
My purpose here is to strengthen Karl Polanyi’s work through critique of and extension to abductive processes. Polanyi presented history woven into a new paradigm for analysis of socioeconomic systems, demonstrated discovery similar to abductive processes, and extended abduction into a holistic context. One of Polanyi’s most important contributions to socioeconomic analysis is the explanation of three integrated network models of socioeconomic reciprocity. They are coadjuvancy, redistribution, and market exchange. Polanyi extended abductive reasoning in two ways. First, he extended it beyond the cognitive logic of a person to inferences and societal belief changes of institutions. Second, he showed that, in the real world, beliefs are not only fixed like an abductive process, they are fixed in law. Throughout Polanyi’s historical presentation, market beliefs are being revised, thus serving as a demonstration of the abductive process. I make both positive and negative critique of a number of Polanyi’s concepts, with special attention to reciprocity, the double movement, and freedom. This critique and abduction extension strengthens Polanyi’s paradigm for future socioeconomic analysis with his integrative network models.
Economics
Keywords: abductive logic; beliefs; double movement; economic theory; freedom; production; reciprocity; reciprocity (commerce); socioeconomic; socioeconomics; stock exchanges

Basic Income, Full Employment, and Social Provisioning: Some Polanyian/Keynesian Insights - Seccareccia, Mario (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
The purpose of this article is to offer a Polanyian perspective on the issue of guaranteed income (GI). In analyzing the debate over the Speenhamland system, especially as Karl Polanyi ([1944] 2001) describes it inThe Great Transformation, he offered an important criticism of a GI program that some contemporary Polanyian economists have been struggling to come to terms with in their writings. Instead of defending a GI policy by seeking to reject Polanyi’s analysis of the problem, I suggest that we should consider embracing Polanyi’s concern by proposing a comprehensive twin policy that would complement a basic income program with a Keynesian full employment commitment.
Economics
Keywords: English Poor Laws; Keynesianism; Speenhamland system; basic income; economists; full employment; full-time employment; guaranteed annual income; income; income supplementation

Provision of Social Costs and the Free Market: A Polanyian Perspective - Vidal, Gregorio; Marshall, Wesley; Correa, Eugenia (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
In this article, we analyze at a conceptual level some of the more relevant effects of the neoliberal takeover on the provision of social costs, including employment, health care, and nutrition. Adopting key perspectives of Karl Polanyi and other thinkers, we develop our examination under the seemingly perpetual conflict between markets and social reproduction. We argue that financialization has both expanded market spaces and changed relationships within those spaces. The ever-greater domination of financial markets means that employment has become increasingly more precarious in the strict spaces of the labor market. At the same time, financialization has steadily eroded the social forms that exist outside of formal markets, greatly weakening the mechanisms through which societies can both defend themselves from predatory markets and reproduce themselves with some degree of purpose and hope for the future.
Economics
Keywords: employment (economic theory); externalities; externalities (economics); financialization; free enterprise; neoliberalism; nutrition; social reproduction

Karl Polanyi et l’encastrement politique de l’économie : pour une analyse systémique des rapports changeants entre économie et société, Karl Polanyi and political embeddedness of economy: a systemic analysis of the changing relationships between economy and society - Chochoy, Nicolas (Revue Française de Socio-Économie, 2015)
Cette contribution défend la thèse selon laquelle une interprétation fidèle de l’encastrement au sens de Karl Polanyi nécessite une analyse qui se positionne dans la relation existante entre l’économie et l’institution organisatrice du social. Cette proposition s’étaye sur une analyse systémique des rapports changeants entre économie et société qui éclaire le désencastrement comme processus d’extériorisation du Marché imaginaire autorégulateur. Face à ce processus, l’enjeu d’une économie solidaire nous semble être de créer les conditions d’une réelle auto-organisation démocratique., This paper defends the idea that a faithful interpretation of Karl Polanyi’s embeddedness requires an analysis at the level of the relationships between economy and the institution which organises the social. This proposal is based on a systemic analysis of the changing relationships between economy and society that considers the disembeddedness as an externalisation process of imaginary self-regulating market. In front of this process, the issue of solidarity economy seems to be the creation of conditions for a real democratic self-organisation.
Economics
Keywords: autotranscendance; democracy; démocratie; embeddedness; encastrement; marché; markets; solidarity economy; économie solidaire

La pluralité des logiques d’action de la Banque Palmas au Brésil : entre développement local et partenariats au niveau national, The plurality of Banco Palmas’ strategies: between local development and partnerships at a national level - Meyer, Camille (Revue Française de Socio-Économie, 2015)
Actives dans plus de 100 communautés au Brésil, les banques communautaires de développement représentent un phénomène majeur de l’économie solidaire brésilienne. En se référant aux apports théoriques de Karl Polanyi, cet article propose une analyse des logiques d’action plurielles de la première banque communautaire de développement brésilienne, la Banque Palmas., Effective in more than 100 communities in Brazil, community development banks are a major phenomenon of Brazilian solidarity economy. Referring to the theoretical contributions of Karl Polanyi, this paper proposes an analysis of the plural organizational logics of the first Brazilian community development bank, Banco Palmas.
Economics
Keywords: Brésil; banque communautaire de développement; finances solidaires; social economy; économie plurielle

To boldly go (Fund Strategy, 2015)
The article provides the author's view on issues concerning free market economics. He mentions Mr. Spock, a fictional character in the "Star Trek," whom critics of free market economics often cite as the epitome of rational economic man or Homo Economicus, as well as features Karl Polanyi, a Hungarian-American economist, who opposed the idea of humans as rational economic agents in his work "The Great Transformation." He also mentions human reason and cultural pessimism.
Economics
Keywords: Spock; Mr.; capitalism; economists; free enterprise

Critique and transformation: On the hypothetical nature of ecosystem service value and its neo-Marxist, liberal and pragmatist criticisms - Melathopoulos, Andony; Stoner, Alexander (Ecological Economics, 2015)
Ecosystem service valuation (ESV) attempts to transform the opposition of human economic necessity and ecological conservation by valuing the latter in terms of the services rendered by the former. However, despite a number of ESV-inspired sustainability initiatives since the 1990s, global ecological degradation continues to accelerate. This suggests that ESV has fallen far short of its goals of sustainable social transformation—a failure which has generated considerable criticism. This paper reviews three prominent lines of ESV criticism: 1) the neo-Marxist criticism, which emphasizes the “fictitious” character of ecosystem commodities; 2) the liberal criticism through Friedrich Hayek's concept “scientistic objectivism”; and 3) the pragmatist criticism of “value monism”. Although each form of criticism provides insight into the limitations of ESV, all share ESV's inability to discern what kind of social transformation is possible . Unable to provide an account of their own immersion in social and historical context, these approaches operate in the hypothetical . In light of these shortcomings, this paper advances a critical theory approach, which we contend provides conceptual tools uniquely well-suited to more adequately address the question of social transformation.
Economics
Keywords: Marxian economics; ecosystem services; neoliberalism; pragmatism; social development

Le syndicat chinois: Une institution au coeur du rapport salarial. (The Chinese Trade-Union: A Core Institution of the Wage-Earning Relationship. With English summary.) - Perisse, Muriel (Mondes en Developpement, 2015)
The official Chinese Trade Union has gained strength during the reforms, to the point that it must be considered as a central institution of the contemporary Chinese wage ratio. As a quasi-governmental organization, it belongs to the evolutionary institutional design and must find new solutions to the labor problems resulting from the reforms. However, its creativity only produces organizational solutions that are far from achieving a real counter-movement in a Polanyian sense.
Economics
Keywords: countermovement; economic development: human resources; economic integration; human development; income distribution; industry studies; international linkages to development; migration; population; role of international organizations; socialist institutions and their transitions: international trade; finance; investment; relations; and aid P33; socialist systems and transitional economies: factor and product markets; wage differentials; wage level and structure

Towards a neo-Polanyian approach to money: integrating the concept of debt - Saiag, Hadrien (Economy & Society, 2014)
This paper aims to reconsider Polanyi's approach to money. His best-known writing on money uses is deeply original and presents strong insights that dissociate money from the concept of the market. Polanyi also developed an interesting non-dichotomous understanding of money in hisThe great transformation. However, taken together, these two contributions lead to some unresolved questions: his critique of the orthodox approach to money is ambivalent; his argument to separate payment from account is weak; and, most important, he ultimately makes an incomplete break with the classical real/monetary dichotomy. This paper proposes a distinction between money as a set of instruments and practices and money as a concept, through the integration of John Commons's concept of debt into Polanyi's framework. This reformulation allows us to resolve Polanyi's unresolved questions while preserving his major contributions, and leads to a more complex understanding of money.
Economics; Anthropology
Keywords: COMMONS; J.R.; COMMONS; John; Great Transformation; The (Book); debt; debt management; economic anthropology; economic aspects; economics; money plurality; political aspects; theories of money

The Precariat - Standing, Guy (Contexts: Understanding People in Their Social Worlds, 2014)
Economist Guy Standing explains how millions of people are in the precariat, and in defining this emerging class, points to the dangerous political and social consequences as well as the exciting progressive revival that this class could produce.
Economics
Keywords: Great Transformation; The (Book); POLANYI; Karl; 1886-1964; class inequality; economics; labor; labour; politics; precariat; precarity; social classes; welfare economics

Socioéconomie et démocratie – l'actualité de Karl Polanyi Isabelle Hillenkamp & Jean-Louis Laville (éd.) - Maucourant, Jérôme (Revue de philosophie économique, 2014)
A book review in a French journal
Economics
Keywords: book review; economic philosophy

Class Struggle or Embedded Markets? Marx, Polanyi and the Meanings and Possibilities of Social Transformation - Selwyn, Benjamin; Miyamura, Satoshi (New Political Economy, 2014)
Marx and Polanyi both held that socialism, in one form or another, was a preferable and possible alternative to capitalism. Their ideas are seen to offer theoretical tools to understand the tensions and contradictions of capitalism, and to inform ways to overcome them. This paper discusses Polanyi's work from a Marxist perspective in order to illuminate his strengths and weaknesses. Its main focus is to discuss Polanyi's juxtaposing of commodification against exploitation, in diagnosing the problems of capitalist expansion. We suggest that by juxtaposing these two moments, Polanyi not only misses out on a crucial arena of capitalist activity (exploitation), but also undermines his own explication of processes of commodification. This has deleterious consequences for his understanding of the prevalence of poverty under capitalism. It also means that his vision of social transformation and of socialism is profoundly different, and potentially antithetical, to that of Marx. We suggest that for Polanyi's conception of de-commodification to gain greater traction it needs to be combined with Marx's analysis of exploitation and class struggle.
Political Science; Economics
Keywords: MARX; Karl; 1818-1883; Polanyi; commodification; exploitation; historical materialism; institutionalism

Understanding the Precariat through Labour and Work - Standing, Guy (Development and Change, 2014)
This article sets out a framework for analysing the globalizing labour process, arguing that the old dualisms of ‘capital’ versus ‘labour’ and ‘formal sector’ versus ‘informal sector’ are inadequate and unhelpful. It begins by making conceptual distinctions between work and labour and between labour and labour power, and goes on to identify a globalizing class structure in which a ‘precariat’ is emerging as a potentially transformative new mass class. Denied so-called ‘labour rights’ and social entitlements that went with twentieth century industrial citizenship, the growing precariat needs new systems of regulation, social protection and redistribution. These should be based on work and occupation rather than subordinated labour, will require new forms of collective action and representation, and should seek to redistribute the key assets of twenty-first century tertiary societies, including income security, control of time, financial capital and the commons. INTRO: That should be the starting point in trying to come to terms with what has been happening in the ‘Global Transformation’, the painful construction of a global market system, analogous to Karl Polanyi's Great Transformation (1944), which was about the construction of national market systems. The Global Transformation, in which the globalization era may be seen as the disembedded phase, has yielded global class fragmentation, or a globalizing class structure superimposed on preceding class structures across the world. This contention has raised the hackles of some Marxists adhering to nineteenth century imagery. But understanding twenty‐first century developments is surely easier if we see a more nuanced structure than the old Marxist dualism of capitalist (bourgeoisie) and proletariat.
Economics
Keywords: precariat

Le don fondateur du lien social, le cas de l'économie de marché - Lasida, Elena (Transversalités, 2014)
Le don et l’échange marchand sont généralement opposés. Pourtant, l’un et l’autre apparaissent comme fondateurs du lien social dans la mesure où l’on prend en compte la relation qu’ils créent au niveau interindividuel et collectif. Le don apparaît ainsi associé à une certaine forme de réciprocité et le marché à une certaine forme de gratuité., Gift and commodity exchange are generally opposed. But both appear as founders of the social bond when we consider the relationship they create between people and in society. The gift is thus associated with some form of reciprocity and the market with some form of gratuitousness.
Sociology; Economics
Keywords: don; lien social; marché; relation; réciprocité; valeur; économie; économie sociale et solidaire

Innis and Polanyi: The Search for the Substantive Economy - Rotstein, Abraham (Journal of Economic Issues; Abingdon, 2014)
Economics and the economy have an uneasy relationship. Economics is akin to the logic of mathematics in contrast to the term "economy," which is an institutional framework to provide for material wants. While they overlap in the modern market economy, economics provides distorted results when applied to tribal societies, the economies of antiquity, or modern state-organized economies. Harold A. Innis and Karl Polanyi both attempted to find a different conceptual framework for a truly general economic history. [PUBLICATION ABSTRACT]
Economics
Keywords: INNIS; Harold; business & economics - economic systems and theories; economic history; substantiveness; supply and demand

Género y cuidados: respuestas sociales e institucionales al surgimiento de la sociedad de mercado en el contexto europeo - Carbonell Esteller, Montserrat; Gálvez Muñoz, Lina; Rodríguez Modroño, Paula (GENDER AND CARE: SOCIAL AND INSTITUTIONAL ANSWERS TO THE DEVELOPMENT OF THE MARKET ECONOMY IN EUROPE., 2014)
This article examines from a care approach the social and institutional responses to the development of the market economy in the European context. Studying this long period -which Polanyi called the double movement- is relevant because it constitutes the historical process by which the interests of the market, the logic of profits and its social and scientific naturalization come to dominate. Since then, the importance of care work in people's life, the reproduction of the labour force, and the provision of welfare and social insurance have been ignored. Until very recently, historical analyses have focused on the emergence of the Welfare State, regardless of how the state's answers interacted or modeled with other spheres of welfare provision, especially the family through women's unpaid work. The article focuses on the European experience and the period analyzed comprehends the disintegration of communal and assistance care with the Old Regime Crisis, the development of charity and associations as solutions to the inhibition of the Liberal State in the 19th century -solutions that were limited and insufficient, leading to the state assumption of the care and assistance functions, embryo of the development of later Welfare States after World War II. (English)
Economics
Keywords: capitalismo liberal; care; cuidados; estados del bienestar; gender; género; liberal capitalism; modelos asistenciales pre-industriales; pre-industrial mutual aid regimes; welfare state

Los conceptos más importantes en el trabajo de Karl Polanyi y su relevancia contemporánea - Polanyi Levitt, Kari (Economía y Desarrollo, 2014)
El artículo se centra en la vida y obra del historiador Karl Polanyi, quien escribió el libro "La Gran Transformación", en 2014 y también discute la investigación realizada sobre la vida económica de las sociedades primitivas por Polanyi.
Economics; Development Studies
Keywords: Great Transformation; The (Book); primitive societies

Crisis del modelo neoliberal, hacia una planificación regional. Un aporte polanyiano - Valderrama Saud, Paula (Crisis of the Neoliberal Model; Towards Regional Planning - a Polanyian Contribution., 2014)
Using Karl Polanyi's analytical instrument, I argue that the current withdrawal of the industrialized powers and the emergence of alternative policies in Latin America are determined by the crisis of the neoliberal model. The polarity between democracy and the market, observed since the beginnings of liberal capitalism, has deepened since the inter-war period due to the appearance of so-called "mass democracy." Since that period, foreign policies of industrialized countries have derived from social conflict caused by this polarity. Current neoliberalism, which favors the limitation of democracy in favor of the self-regulating global market, is a system that contains inherent contradictions on financial and socio-political levels. These contradictions are the cause of the current crisis in the United States and the European Union, a crisis that favors the beginning of a new era characterized by greater regional planning and a plurality of development paths. (English)
Economics
Keywords: European Union; Latin America; crisis; democracia; democracy; globalization; government policy; market; mercado; neoliberalism; neoliberalismo; planificación regional; regional planning

Sovereign Debt Restructuring in the Eurozone: A Polanyian Reading of Private Law Enforcement - Thomas, Dania (Studies in Law, Politics & Society, 2013)
The social protests ort the streets of indebted sovereigns in crises across the Eurozone have made debt restructuring an imperative. Further delay in achieving this expeditiously and equitably significantly exacerbates the social costs of crises from which current and future generations will struggle to recover. This article examines the feasibility of the drastic and widespread debt restructuring needed to resolve the problem in the face of existing private law sanctions that protect individual creditor rights. It relies on an analysis of US policy in the transition to a securi-tized market and of key sovereign debt cases to reveal the historical con-tingency of private law protections. It concludes by showing that the effectiveness of private law protections have always been constrained by the overriding imperative to achieve debt sustainability with negotiated and consensual workouts. This can be achieved in the Eurozone with stat-utory constraints on enforcement action pending the settlement of debt workouts as suggested in a recent proposal.
Economics; Law
Keywords: European Sovereign Debt Crisis; 2009-; Eurozone crisis; Eurozone debt crisis; POLANYI; Karl; 1886-1964; US debt litigation; civil law; contingency theory (management); international finance; private law enforcement; securitization; sovereign bond contracts; sustainability

Pi̇yasa: Adam Smith Versus Karl Polanyi̇ - Gökten, Yeliz SARIÖZ (Academic Review of Economics & Administrative Sciences, 2013)
In this study author will try to make comparative analysis of Adam Smith and Karl Polanyi's ideas about market. According to Smith market is a mechanism which allocating resources through invisible hand. Contrary to Smith, Polanyi, asserts that a market is a intervention style to economy. Intervention is an inherent property of market. In the first part of this study Adam Smith's opinions about market which assings limited duty to state and defends social interest will come true through invisible hand will be examined. Second part will concentrate on Karl Polanyi's arguments against appear of market society and market economy. At the end of the study, the author has tried to analyse two different market conceptualization and to assert how well this approaches to understand our times. (English)
Economics; Sociology
Keywords: Piyasa; Piyasa Sistemi; SMITH; Adam; 1723-1790; comparative studies; economic research; economists; market; market system

The Institution, the Economy and the Market: Karl Polanyi's Institutional Thought for Economists - Maucourant, Jerome; Plociniczak, Sebastien (Review of Political Economy, 2013)
This paper aims to clarify the logical structure of Karl Polanyi's concept of institution, especially with regard to his most important contribution to political economy—the conception of self-regulating markets as institutions. Although Polanyi did not provide a well-developed concept of institution, this article argues that such a concept exists in his work. Moreover, there is in Polanyi's work a sophisticated institutionalist account of the self-regulating market that has been largely overlooked as Polanyi does not present it explicitly. Analyzing the economy as an institutionalized process, as Polanyi does, reveals that the market is neither a natural nor a spontaneous phenomenon—a conclusion that runs counter to conventional economic thinking. Polanyi's approach enables us to view capitalism (the ‘market society’ in Polanyi's language) through a highly specific cultural fact: the fiction of the self-regulating market. This institutional perspective needs to be reassessed beyond new-institutionalist theoretical constructions.
Economics; Sociology
Keywords: economic structure; free enterprise; institutions (philosophy); philosophy of economics; social facts

'Marketless Trading in Hammurabi's Time': A Re-appraisal - Dale, Gareth (Journal of the Economic & Social History of the Orient, 2013)
In this article I revisit Karl Polanyi's writings on ancient Mesopotamia. I begin by situating them in the context of his general approach to trade, markets and money in the ancient world. Next, I reconstruct his major theses on Mesopotamia, drawing upon his published works as well as unpublished documents in the Karl Polanyi and Michael Polanyi archives. Finally, I provide a critical assessment of the merits and demerits of his contribution, with reference to Assyriological research published in the decades that have elapsed since his death in 1964.
History; Economics
Keywords: Mesoporamia; Mesopotamia; ancient history; assyriology; commerce; economic history; historiography; history; markets; money; trade

Homo Economicus and the Economics of Property Rights: History in Reverse Order - Milonakis, Dimitris; Meramveliotakis, Giorgos (Review of Radical Political Economics, 2013)
This article challenges some fundamental propositions of property rights theory by revealing the inability of new institutional economics to fully grasp the notion of property, as reflected in its narrow and problematic definition of property rights. The concept of property relations is proposed as better suited to capture the social and institutional aspects of property. By reconsidering the case of the Montagnais, originally used by Alchian and Demsetz for illustrative purposes, and drawing on the works of Polanyi and McManus, we show that the historical explanation of the emergence of (private) property rights provided by Alchian and Demsetz is flawed.JEL Codes: D02, D23, P14
Economics
Keywords: civil rights; economics; emergence; historical specificity; homo economicus; human rights; institutional economics; property; property relations; property rights; redistribution

The Economic-Environment Relation: Can Post-Keynesians, Regulationists and Polanyians Offer Insights? - Chester, Lynne; Paton, Joy (European Journal of Economics and Economic Policies: Intervention, 2013)
As the environmental debate has intensified, post-Keynesians, Regulationists and Polanyians remain relatively silent. All treat time as historical, consider economic issues subordinate to politics and have plenty to say about growth, institutions, uncertainty, and path-dependent events. These concepts seem pertinent to understanding the economic-environment problematic. This article explores the 'environmental potential' of these three heterodox economic traditions. We examine the conception of nature underpinning each methodological approach and the ability of their key conceptual tools to explain the economic-environment relation. Methodological pluralism and a project driven by the neoclassical agenda, we posit, seriously weakens the possibility of a post-Keynesian-grounded coherent environmental perspective. On the other hand, the Regulationists and Polanyians provide cogent analytical frameworks to advance explanations of the economic-environment relation and the contemporary environmental challenge.
Economics
Keywords: Keynesian; Keynesianism; Sraffian; capitalist systems; current heterodox approaches: institutional; economic methodology; environment and development; environment and trade; environmental accounts and accounting; environmental economics: government policy; environmental equity; evolutionary; general aggregative models: Keynes; general aggregative models: Marxian; institutional; political economy; population growth; post-Keynesian; sustainability

A Critique of Economic Determinism: Karl Polanyi's Methodology. (In Russian.) - Nureev, R. M. (Zhournal Novoi Ekonomicheskoi Associacii/Journal of the New Economic Association, 2013)
Economics
Keywords: economic determinism

Karl polanyi and the economicist hybris of modernity - Polo Blanco, Jorge (Logos (Spain), 2013)
Using the work of Karl Polanyi as its axis, this study attempts to sketch a criticism of economicism and of the society that produces it, a society launched on a historical cultural path that may well be understood as a gradual economic totalization of human life. That is the critical path which will be posed here, if only in an embryonic manner.
Economics
Keywords: economic determinism; economic totalization; economicism

Mechanism of Governance of Economic Relations - Rus, Andrej (Teorija in Praksa, 2012)
The problem of the governance of economic transactions arises from the fact that they are sequential. This creates uncertainty regarding the fulfilment of implicit or explicit contracts. Institutional economics understands this uncertainty as arising from opportunism and seeks a solution in specialised contract enforcement institutions. Economic sociology understands the uncertainty as a result of misunderstanding and finds a solution in mechanisms of governance that, in addition to sanctions, allow for coordination among participants in a transaction. In this paper, we confront the arguments made by sociology and economics regarding the mechanism of governance of economic transactions. Following Polanyi, we distinguish three governance mechanisms of economic relations and note that, to be operational, each of them requires a different social structure and social regulation.
Sociology; Economics
Keywords: economic activity; economic sociology; economics; governance mechanisms; institutional economics; social structure; socioeconomics

Mehanizmi Upravljanja Ekonomskih Odnosov - Rus, Andrej (MECHANISM OF GOVERNANCE OF ECONOMIC RELATIONS., 2012)
The problem of the governance of economic transactions arises from the fact that they are sequential. This creates uncertainty regarding the fulfilment of implicit or explicit contracts. Institutional economics understands this uncertainty as arising from opportunism and seeks a solution in specialised contract enforcement institutions. Economic sociology understands the uncertainty as a result of misunderstanding and finds a solution in mechanisms of governance that, in addition to sanctions, allow for coordination among participants in a transaction. In this paper, we confront the arguments made by sociology and economics regarding the mechanism of governance of economic transactions. Following Polanyi, we distinguish three governance mechanisms of economic relations and note that, to be operational, each of them requires a different social structure and social regulation. (English)
Sociology; Economics
Keywords: economic activity; economic sociology; ekonomska sociologija; governance mechanisms; institutional economics; international economic relations; mehanizmi upravljanja; social structure; socioeconomics

An Analytical Framework for the Relationship between Environmental Measures and Economic Growth Based on the Regulation Theory: Key Concepts and a Simple Model - Okuma, Kazuhiro (Evolutionary and Institutional Economics Review, 2012)
This paper proposes an analytical framework using the regulation approach and consisting of explanations of some concepts and a simple way of modeling; the concepts and modeling are developed by focusing on the distributive aspect of environmental issues and using environmental costs as key indices. As a basis for the framework, we refer to the ideas of Polanyi and the surplus approach, and we recognize the socio-economic system as interlinked triple reproductions of the economy, humans, and the environment. This recognition is formalized as an equation of three-dimensional distributions among profits, wages and rents. The "economy-environment nexus," which represents the relationship between the natural environment's reproduction and economic reproduction, is analyzed as one of the institutional forms. The dynamics of institutional coordination are specified with attention to distributive conflicts between relevant actors, leading to the idea of "spatial and temporal gaps of coordination." Environmental costs are identified and incorporated into the equation of distribution as key information to characterize specific forms of the economy-environment nexus. The economy-environment nexus influences growth regimes through multiple routes, including investment, trade, and productivities. In order to analyze the aggregate effects, we propose a variant of the Kaleckian growth model incorporating environmental costs as key variables. Using this model, we specify conditions for the "paradox of costs for environmental measures," where environmental measures raise the profit rate. This framework is expected to be used in historical or comparative analyses of particular economies, including those using periodized specification of the economy-environment nexus.
Economics
Keywords: Marxian; Sraffian; current heterodox approaches: socialist; distributional effects; employment effects; environment and development; environment and growth; environment and trade; environmental accounts and accounting; environmental equity; pollution control adoption costs; population growth; sustainability

China's Decentralized and Inegalitarian Developmental State - Nordhaug, Kristen (Forum for Development Studies, 2012)
This article investigates China's market reforms and rapid economic development from the late 1970s. The following questions are posed: (1) How did the Chinese 'peasant revolution' and the rural policies and institutions of Mao China influence the market reforms and subsequent economic development? (2) How does China's development after the market reforms relate to Marxist and Polanyian notions of proletarization and commodification of land and labour as preconditions of capitalist development? (3) To what extent and why does China's development after the market reforms diverge from East Asian growth with equity? (4) How does China's 'decentralized developmental state' influence its growth model and distribution? (5) The present Chinese government tries to promote greater equality and more domestic consumption. Is this a Polanyian 'double movement' in response to commodification of land and labour? How likely are these policies to succeed? These questions are addressed through historical-comparative analyses with comparisons of long-term rural dynamics of Mao China and the former Soviet Union. China after the market reforms is compared with England during its transition to agrarian capitalism and industrial capitalism from the sixteenth century through the early nineteenth century and with Taiwan and South Korea from the late 1940s until the 1980s.
Development Studies; Economics
Keywords: Marxian; Sraffian; aggregate factor income distribution; current heterodox approaches: socialist; inflation; institutions and growth; institutions: design; formation; and operations; macroeconomic analyses of economic development; money; socialist systems and transitional economies: national income; product; and expenditure; structure; scope; and performance of government

As especificidades da mercadoria força de trabalho: Marx revisitado - Antonio Vieira, Pedro (The specifities of the labor power commodity: Marx revisited (the labor power commodity: Marx revisited., 2012)
Coming along with Polanyi's ideas of fictitious commodity, this paper seeks to reveal the logical inconsistencies and silents in the economic science arguments on the labor force as a commodity. Once Marx's influence on the anti-capitalist movements is outstanding, we need to show his contribution, through his economic thought, to the scientific economism. As is well known, when proposed that the commodity sell by the worker was the 'labor force' instead the labor, as the classical economists used to say, Marx was able to built his theory on the capitalist economy theory, which relies on the concept of surplus value.. That is the reason why the paper is specially concern with the failures or weaknesses present in one of the huge Marx contribution to the economics thought: the concept of labor force. (English)
Economics
Keywords: MARX; Karl; 1818-1883; anti-globalization movement; capitalists & financiers; commercial products; economics; economism; economists; fictitious commodities; labor force; labor supply; labor-market; labour force; labour market; labour supply; political economy

L'idéologie marchande au service de la biodiversité ? - Tordjman, Hélène; Boisvert, Valérie (Mouvements, 2012)
Economics
Keywords: biodiversity; markets

Retour sur le désencastrement - Brisset, Nicolas (Revue européenne des sciences sociales. European Journal of Social Sciences, 2012)
Our ambition is to point out that a fresh look at what is usualy considered to be Karl Polanyi’s magnum opus, The Great Transformation, opens some new prospects on its analytical. This interpretation qualifies some of the Hungarian author’s main critics, directed against his concept of desembeddedness. With this aim in mind, we re-interpret this debate in epistemological terms, i.e. the link between concepts and reality ; then we try to connect Karl Polanyi with the notion of performativity, which is today flourishing, above all within the field of economic sociology.
Economics
Keywords: Great Transformation; The (Book); Karl Polanyi; disembeddedness; great transformation; performativity; realism

Crise ? Vous avez dit : « Crise » ? - Naszályi, Philippe (Revue des Sciences de Gestion, 2012)
Crisis and institutional environment, crisis and organisational anticipations and crisis and consumer behaviour, just a few of the uses of the word « crisis » ; a word which, for over four years now, for the less perspicacious, and for over thirty years, for those who have been watching the bigger picture, has been the most appropriate word for this stage of development of the contemporary economic system. But exactly « what crisis are we talking about? ». That which is the result of a system, of an ideology which inhabits this system and of which the slightest of abilities was to try and present itself as unable to be exceeded, « by the end of the story ».' Yet, just as Max Weber stated, it seems that today's knowledge is still destined to be exceeded, particularly in the humanities, since society is constantly undergoing transformation. There is, therefore, no economic model which should not be discussed in order to be improved, or replaced. By delving into the ideal of Sismondi, today wrongfully forgotten, or in studying Karl Polanyi, we can gain much support for contemporary reflection which cannot continuously oppose Keynes, often summarised to the deficit of public policies and the « Chicago Boys » of which the action with Augusto Pinochet is truly symbolic of this « neo-liberalism» of American conservatives which is spreading across the globe, despite the crises which it has created. Crisis? Did you say: « Crisis' ? A question, and observation, but also in the manner of «great thinkers », solutions and alternatives which managers, in the widest sense of the term, « those who look after others and their businesses », provide through thirteen articles, collated into three thematic sections in this Spring edition which opens up new areas for reflection and action as « it is indeed time to put production before speculation, future investment before current satisfaction, sustainable employment before immediate profiteering ». (English)
Economics
Keywords: WEBER; Max; 1864-1920; consumer behavior; economic models; economic systems; humanities; institutional environment

The Fundamental and Eternal Conflict - Parguez, Alain (International Journal of Political Economy, 2012)
This contribution aims at exploring what is today the new "normal" in economic policy, namely, austerity. It must be read as a homage to Karl Polanyi, the first who understood the tragedy, and to Kari Polanyi-Levitt, who expanded on her father's thought. Austerity has nothing to do with old anticyclical or stabilizing policies. It is a permanent regime devoid of any sound foundations. It is a pure quasi-religious policy that is self-reinforcing. The author emphasizes the fundamental conflict between its promoter, Friedrich Hayek, and its adversary, John Maynard Keynes, and points to the sole towering intellectual, Karl Polanyi, who understood that their conflict embodied two radically different visions of the world. Polanyi discovered that the core of the conflict was the merciless fight between the supreme rule of God-given market laws, the Hayekian order, and democracy enshrined in a peaceful society that is oriented toward the future. The Hayekian order abolishes the modern democratic state, sacrifices the future, and extols poverty for the sake of order. Polanyi was the first to have discovered the true message of Keynes, who had destroyed the logical foundations of Hayek's philosophy and economics. In conclusion, the author strives to explain why, early in the twenty-first century, the Hayekian legacy is the true road to serfdom because it ignores Polanyi and encourages belief in market laws. Early American "Keynesians," who knew nothing about Hayek, transformed Keynes into a new Léon Walras. These early Keynesians were doomed from the start and vanished when they endorsed the Philips curve as expressing the absolute truth.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; KEYNES; John Maynard; 1883-1946; Keynesian economics; The General Theory of Employment; Interest & Money (book); austerity; banking industry – Social aspects; consumption (economics); economic history; employment (economic theory) - social aspects; equilibrium (economics); flexibility; free enterprise; government policy; history of economics - 20th century; international political economy; investments - social aspects; market laws; mixed economy - social aspects; money; money - social aspects; scarcity - social aspects; state

Critique of Current Neoliberalism from a Polanyian Perspective-Politics, Philosophy, and Economics - Seccareccia, Mario (International Journal of Political Economy, 2012)
An introduction is presented which discusses articles within the issue on topics including neoliberalism, the Austrian economist Karl Polanyi's perspective on the history of industrial society during the nineteenth and twentieth centuries and free enterprise.
Economics; Political Science
Keywords: POLANYI; Karl; 1886-1964; free enterprise; neoliberalism; political economy

Embedded Markets: A Dialogue between F.A. Hayek and Karl Polanyi - Migone, Andrea (Review of Austrian Economics, 2011)
The recent economic crisis has once more underscored the close connection between markets and social life, thrusting this point at the centre of the analysis of economic and political activity and has once more asked the question of whether and how individuals are embedded in both. Here I argue that an analysis and partial reconciliation of the positions of F. A. Hayek and Karl Polanyi on the topic can help in this debate.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; capitalist systems; embedded markets; history of economic thought

Penser l’institution et le marché avec Karl Polanyi - Maucourant, Jérôme; Plociniczak, Sébastien (Revue de la régulation. Capitalisme, institutions, pouvoirs, 2011)
Bien que Karl Polanyi (1886-1964) n’ait jamais eu pour ambition « d’élaborer une théorie complète des institutions économiques », ce texte met en évidence qu’il y a, dans son œuvre, une analyse aussi implicite que profonde du marché appréhendé comme institution ou « processus institutionnalisé ». À l’encontre de la croyance économique conventionnelle, l’œuvre de Polanyi permet de comprendre que le marché, n’est ni spontané ni autorégulateur. Plus encore, à suivre Polanyi, le capitalisme ou « société de marché » se caractérise par un fait culturel spécifique : la croyance utopique en l’autorégulation marchande. Une origine de la crise économique actuelle peut ainsi être mise en évidence. Plus généralement, tout économiste contemporain soucieux des problématiques de l’institution et du marché peut, avec Polanyi, resituer de façon novatrice les marchés au sein des contextes socio-historiques dans lesquels ils se déploient. ENG translation: Although Karl Polanyi (1886-1964) never had the ambition "to elaborate a complete theory of economic institutions", this text emphasizes that there is in his work an analysis both implicit and profound Market as an institution or "institutionalized process". Contrary to conventional economic belief, Polanyi's work makes it possible to understand that the market is neither spontaneous nor self-regulating. Moreover, to follow Polanyi, capitalism or "market society" is characterized by a specific cultural fact: the utopian belief in mercantile self-regulation. An origin of the current economic crisis can thus be highlighted. More generally, any contemporary economist concerned with the problems of the institution and the market can, with Polanyi, innovatively place markets in the socio-historical contexts in which they unfold.
Economics
Keywords: capitalisme; crise; encastrement; institution; marché autorégulateur; marchés; société de marché; utopie

KARL POLANYI'S METACRITIQUE OF THE LIBERAL CREED Reading Polanyi's Social Theory in Terms of Dialectical Critical Realism - Despain, Hans G. (Journal of Critical Realism, 2011)
This paper interprets Karl Polanyi through dialectical critical realism. The paper maintains that this interpretation offers Polanyi methodological coherence and philosophical support. It further provides dialectical critical realism with an exemplar of explanatory critique. It is argued that the social theory of Polanyi aims at the demystification of market-systems as they are theoretically constructed by both orthodox and heterodox accounts of capitalism. Dialectical critical realism is best capable of situating the theoretical accomplishment of Polanyi's historical and dialectical critiques of social being.
Economics
Keywords: capitalism; critical realism; economic theory; economics; explanatory critique; liberal creed; neoliberalism; ontology; social history; social theory

Les sciences sociales africanistes à l’épreuve des projets de développement. Peuvent-elles dépasser l’opposition entre l’universalisme de l’économie et le relativisme de l’anthropologie ? - Hugon, Philippe (Cahiers d’études africaines, 2011)
RésuméLes disciplines économiques et anthropologiques, notamment africanistes, ont été généralement caractérisées par des exclusions et des cloisonnements. L’économie s’intéresse principalement aux sociétés marchandes et capitalistes occidentales et mobilise des catégories à vocation universelle alors que l’ethnologie ou l’anthropologie prennent pour champ les sociétés « primitives » exotiques ou premières, et privilégient les catégories et représentations des acteurs. Le champ du développement a été un lieu de rencontre obligé des deux disciplines. L’économie a cherché à aborder les sociétés non occidentales et l’anthropologie a été confrontée aux projets de développement. Cet article rappelle les oppositions historiques entre les éclairages économiques et anthropologiques avant de présenter certains enjeux méthodologiques et épistémologiques d’une anthropologie économique du développement en l’illustrant par la filière coton., Abstract ENG: Economics and anthropology as africanist social sciences have known a separate evolution. Economics are mainly interested by capitalism and Western societies and mobilize universalist concepts. Ethnology or anthropology on the other hand study more traditional, “primitive” or exotic societies. Howewer the two meet and have some confrontation when they study development. Firstly, this article recalls the historical oppositions between the economical and the anthropological points of view. Secondly, it presents some of the methodological and epistemological stakes of development economic anthropology. Lastly this paper illustrates this debate in examining the case of the chain value within the economic overall process of coton production and exchange.
Economics; African Studies
Keywords: africanist social science; cotton production; exchange

Karl Polanyi: The Limits of the Market - Barnes, Tom (Journal of Australian Political Economy, 2011)
The article reviews the book "Karl Polanyi: The Limits of the Market," by Gareth Dale.
Keywords: DALE; Gareth; KARL Polanyi: The Limits of the Market (Book); Polanyi; Karl; 1886-1964

Le concept de « marchandise fictive », pierre angulaire de l'institutionnalisme de Karl Polanyi ? - Postel, Nicolas; Sobel, Richard (Revue de philosophie économique, 2011)
The notion of “fictitious commodities” is not simply a convenient heterodox slogan to criticize the radical limits of any trade system and the analytical limits of the dominant theory. It is rather the foundation of the institutional perspectives that underlie all Karl Polanyi’s sociohistoric analyses. This article explains and articulates both the theoretical level using the institutional approach to commodities and a philosophical level using a broad definition of the economy. There is, however, a limit to the notion of the institution, which connects both levels: it is not articulated practically such that the potential and critique of this construct may be weakened.
Sociology; Economics
Keywords: capitalisme; institution; marchandises fictives; raison pratique; économie substantive

Would You Barter with God? Why Holy Debts and Not Profane Markets Created Money - Semenova, Alla (American Journal of Economics and Sociology, 2011)
Attempting to revitalize the substantive approach to economics in the tradition of K. Polanyi, this paper revives the neglected substantive theory of money's origins by Bernhard Laum and thus disputes the formal approaches that see the origins of money in the context of trade. A wide range of evidence, from archeological to etymological, is utilized to demonstrate that relations between men and God, carried out through the intermediary of state-religious authorities, played a causal role in the genesis of the ox-unit of value and account, and, further, in the origins of money, and, subsequently, coinage. The substantive state-religious approach presented in this paper is also compared and contrasted to the Chartalist perspective on money's origins. It is concluded that the substantive approach presented in this paper differs from the more formal approaches (e.g., Metallism) because it does not rely upon a projection of modern institutions and habits of thought (e.g., a medium of exchange; monetary taxation) into ancient societies.
Economics; Sociology
Keywords: ancient societies; money; substantive approach

The Polanyi-Stanfield Contribution: Reembedded Globalization - Brown, Doug (Forum for Social Economics, 2011)
This essay describes and interprets J. Ron Stanfield's analysis of Karl Polanyi. Stanfield has helped to clarify Polanyi's "double-movement" thesis by arguing that the double movement of self-regulating market forces and the protective response is essentially about freedom versus security. These insights provide an analysis that takes Polanyi into the twenty-first century by developing a theory of "reembedded globalization." This is not something that Polanyi experienced before his death in 1964. Corporate globalization and the escalation of free-market rhetoric have led to a new round of disembedding since the 1970s, and this is evident by both the top-down, corporate globalization of privatization, deregulation, and marketization, as well as, by the challenges to it from the "movement of movements" coalescing around the World Social Forum. The most conspicuous evidence of this neo-protective response and its challenge to corporate-driven market forces is that between the security needs of the world's globalization victims and the freedom of transnational corporations to make profits anywhere and in any way throughout the world. Understanding the clash in this way suggests that for humanity to save itself, it must struggle to reembed globalization and put security ahead of unbridled freedom. Reembedding globalization requires asserting democratic security ahead of the economic freedom of big business.
Economics
Keywords: MARX; Karl; 1818-1883; Marxian; Sraffian; capitalist systems; current heterodox approaches; globalization; history of economic thought; international economic order; political economy; reembedded; socialism

Economic Surplus, Social Reproduction, Nurturance and Love - O'Hara, Phillip Anthony (Forum for Social Economics, 2011)
This paper examines the contributions of James Ronald Stanfield to social and political economy. We start the analysis with Stanfield's contribution to institution building through his education of PhD students, building a graduate program in political economy, and through the associations of social and political economy. Then we go on to scrutinise his creative developments and applications of the notions of economic surplus and social reproduction. This is followed by his extensive work on Karl Polanyi and the disembedded economy. Finally we explore his path-breaking analysis of the great capitalist restoration, the nurturance gap and love. Stanfield was one of the greatest institutionalists and social economists of the last hundred years, and these four areas of energetic creativity are his prime achievements in the area.
Economics
Keywords: Marxian; Sraffian; current heterodox approaches: socialist; history of economic thought: individuals

Some Social Economics Concepts for Future Research - Stanfield, James Ronald (Forum for Social Economics, 2011)
Under the guidance of a recrudescent nineteenth century ideology, the governance of the global economy has been profoundly altered in the past three decades; indeed, a veritable Great Capitalist Restoration has emerged. It is important to view the transitioning economies and emerging market economies as part of this massive shift in governance. The concept of economic surplus offers a useful perspective on the political economy of governance regimes. Karl Polanyi's post-Marxian view of lives and livelihood provides important insight into the nature of the Great Capitalist Restoration, its ideologically-driven impetus, and its eventual foundering on the shoals of instability, insecurity, inequality, and social and ecological unsustainability. The ineluctable crisis of the Great Capitalist Restoration provides another opportunity to construct a viable democratic economic future, one that avoids the pitfalls that brought down the corporate-welfare state, and offers more than inauthentic, joyless commodity consumption. To build the Road to this Future, we will need a powerful heterodox economic analysis of agency and governance, guided by a vision of an economy which is subordinate to the lives it provisions.
Economics
Keywords: Marxian; Sraffian; capitalist systems: political economy; current heterodox approaches: socialist; international economic order; social economy

Karl Polanyi's Institutional Theory: Market Society and Its "Disembedded" Economy - Cangiani, Michele (Journal of Economic Issues, 2011)
A fundamental principle of Karl Polanyi's institutional outlook is that any economic system has to be considered as a whole and as a historically specific social organization. This principle implies a comparative method and a critique of conventional economics. Besides, the problem of the interrelation between the economic system and other aspects of social life cannot be avoided. On this basis, Polanyi points out the peculiar "economic" nature of the market-capitalist society and explains the institutional transformations characterizing its history. The opposition "embedded/disembedded," used by Polanyi to distinguish pre-modern economies from the market economy, has been widely adopted in recent times, particularly by economic sociologists, as a key for understanding current complex economic phenomena. However, the reference to Polanyi often presupposes a distorted interpretation of his theory, and a different kind of institutional approach.
History; Economics
Keywords: comparative economics; disembedded economy; economic policy; economic systems; embedded economy; institutional economics; institutional method

Polanyi contre Freeman. (Polanyi against Freeman. With English summary.) - Postel, Nicolas; Sobel, Richard (Revue de la Regulation, 2011)
The dominant approach of CSR is based on the concept of "stakeholders" (R. E. Freeman). More than a theory, it is a slogan which irrigates as much the scientific discourse as the manager and political discourses. We can make two readings of this slogan. The first one, which is very reducing for us, consists on the deconstruction of the firm as institution and its replacement by a market representation based on bilateral exchanges between rational individuals. The second one, more promising in order to identify the potentialities of CSR in terms of regulation, intends to found the notion of stakeholder on a theory of actor and institution. It is the position which we defend by mobilizing Karl Polanyi's institutionalism.
Sociology; Economics
Keywords: Marxian; Sraffian; business objectives of the firm; corporate culture; current heterodox approaches: institutional; current heterodox approaches: socialist; diversity; evolutionary; social responsibility

A contribuição de Karl Polanyi para a sociologia do desenvolvimento rural - Schneider, Sergio; Escher, Fabiano (Sociologias, 2011)
O ensaio aborda a importância da redescoberta do pensamento de Karl Polanyi e de sua crítica à "sociedade de mercado" na retomada dos estudos e debates sobre o desenvolvimento (rural). Após uma apresentação geral do quadro teórico e analítico de Polanyi, buscamos utilizar seus conceitos para interpretar a dinâmica da mercantilização dos meios de vida e das formas sociais de trabalho e produção no espaço rural, bem como dos sistemas agroalimentares no capitalismo contemporâneo. Com base nestas proposições, refletimos sobre o papel dos atores sociais e das instituições nos processos de mudança social em geral e os de desenvolvimento rural em particular. Finalizamos, propondo algumas potencialidades dessa abordagem para os estudos sobre desenvolvimento rural no Brasil. ENG: The essay deals with the importance of the rediscovery of Karl Polanyi's thinking and of his criticism of the "market society" in resuming (rural) development studies and debates. Following an overall presentation of Polanyi's theoretical and analytical framework, we look for using his concepts to interpret the commoditization dynamics of the rural livelihoods and the social forms of labor and production in the rural space, as well as the commoditization of the agri-food systems in the contemporary capitalism. Based on these statements, we reflect about the role of social actors and institutions in the processes of social change at large and of rural development in particular. And, finally, we propose some potentialities of this approach for the rural development studies in Brazil.
Sociology; Economics
Keywords: commoditization; institutions; rural development; social actors

Not Free Emerging of Free Market–'The Great Transformation' by Karl Polanyi. (In Bulgarian. With English summary.) - Sedlarsky, Theodor (Economic Thought, 2011)
An attempt was made to sum up the basic socio-economic issues in Karl Polanyi's book "The Great Transformation", which is less known by the economists in our country. Suggesting an alternative to Marx's market economic analysis at the early stages of establishing and imposing the capitalist social system, this significant work of Polanyi questions at the same time a lot of the postulates of the modern liberal economic doctrines. The study highlights the formation of free market not as a natural process, based on natural human aptitudes, but on the contrary–as forcing a framework of rules, contrary to the traditional social organization of the people.
Economics
Keywords: Bulgaria; Great Transformation; The (Book); Marxian; Marxist; Sraffian; capitalist systems: political economy; current heterodox approaches: socialist; history of economic thought since 1925: socialist; history of economic thought: individuals; review

The Foundation of the Modern National Economy and Discipline over Its Monetary Discourse: A Consideration from the Perspective of Polanyian Economics - Wakabayashi, Shigetaro (Journal of Economic Issues (Taylor & Francis Ltd), 2010)
How does the causality between society and the economy run? After examining this fundamental question from the perspective of Polanyian economics, we conclude that the modern national economy is where bargained exchange is institutionalized by society to pre-exist with the aid of discipline over currency issues. However, this discipline is not provided with a proper institutional defense; and potential fragility of the modern national economy owing to this fact was most vividly revealed by central bankers' conduct in the great liquidity crisis of 2007/8. What are we to do for this?
Economics
Keywords: Polanyi's institutionalism; bankers' associations; banking industry - economic aspects; capitalists & financiers; commercial banking system; crises - economic aspects; currency discipline; discourse; discourse and discipline; liquidity (economics); monetary policy; money; negotiation - social aspects; society and the economy

Power and Progress: The Swing of the Pendulum - Stewart, Frances (Journal of Human Development & Capabilities, 2010)
This paper uses Polanyi's 1944 analysis of policy change—in which there are long-term swings from state regulation to markets and back again, as the consequences of one regime lead to political reactions that in turn reverse the policies. It shows how the Polanyi analysis continued to apply throughout the twentieth and early-twenty-first century, well beyond when he wrote, and that the swings also apply to developing country policy-making. It argues that there are new signs of policy change—this time against market domination—in a number of developing countries. The paper concludes that Polanyi's view of the conditions behind policy change—notably long-term political movements, political struggle and political conflict—needs to be introduced into the analysis of policy change for the promotion of human development and the expansion of capabilities.
Development Studies; Economics
Keywords: developing countries; government policy; human development; legislation; policy sciences; policy swings; political economy; political planning

Globalisation and the Commodification of Labour: Temporary Labour Migration - Rosewarne, Stuart (Economic and Labour Relations Review, 2010)
There has been a qualitative shift in the character of international labour migration with increased temporary labour migration. With circumscribed employment rights, the increased significance of temporary migrant workers underscores arguments that globalisation has engendered a more profound commodification of labour. The instrumentalist approach, especially of international financial institutions in promoting temporary labour migration as a panacea for development, reinforces this impression. Encapsulated in migration-development discourse, labour migration, like other commodities, is presented as a means of generating export revenue for the South. Karl Polanyi's critique of this market-defined construct of labour as a commodity, when labour can only ever be a fictitious commodity, provides a basis for contesting the representation of labour in the migration-development discourse. However, recourse to a Marxist method is held to be essential if we are to move beyond an appreciation of the process in order to interrogate the rationale that is driving the transformation of labour.
Economics
Keywords: Marxian; Sraffian; commodification; current heterodox approaches: socialist; fictitious commodities; geographic labor mobility; globalization; immigrant workers; labor migration; labour migration; migrant; migrant workers; migration; value theory

L’Encastrement Social des Marchés. Éléments théoriques et empiriques pour une analyse en termes de réseaux relationnels - Plociniczak, Sébastien (Revue de la régulation. Capitalisme, institutions, pouvoirs, 2010)
Despite the core role played by market in economic theoretical frameworks, the market is still little addressed and finally remains a vague type at best equivoque. This thesis aims to contribute to a collective pattern devoted to the diversification of market analysis since the 70s. This collective pattern is the New Economic Sociology, founded and built on a central idea, i.e. the embeddedness. In the perspective of Karl Polanyi and Mark Granovetter’s works, the thesis intends thus to enlighten first the use of this idea as the necessary clarification does not occur until now. Then, it puts forward the fact that an analysis of markets may definitely benefit from a deeper understanding of the multilateral logic of relational networks. At last, on the base of main assumptions defined in this thesis, the robustness of the heuristic contractual model of the Transaction Costs Economics depicted by Oliver E. Williamson is assessed.
Economics
Keywords: capital social; contrat; coûts de transaction; embeddedness; encastrement; forme hybride; institutions; marchés; réseaux relationnels; social capital

Hannah Arendt et Karl Polanyi : le libéralisme économique, l'effondrement du politique et la société de masse, Abstract - Azam, Geneviève (Revue du MAUSS, 2010)
RésuméDans les années 1930, Hannah Arendt et Karl Polanyi ont partagé l’expérience du déracinement, de la désolation et celle de l’effondrement de la civilisation du xixe siècle. À partir de l’analyse de la société de marché pour K. Polanyi et de la condition de l’homme moderne pour H. Arendt, ils montrent comment l’économisme et la construction d’une société économique au xixe siècle, sont à l’origine de l’avènement de la société de masse qui porte des tendances totalitaires. Leur regard croisé donne des clés de compréhension des menaces qui pèsent qui pèsent sur nos « sombres temps »., In the 1930s, H. Arendt and K. Polanyi shared the experience of rootlessness and the collapse of nineteenth century civilisation. Through the analysis of the market society (K. Polanyi) and the condition of modern man (H. Arendt), they analyse how economicism and the advent of an economic society in the nineteenth century have engendered mass societies which carry totalitarian tendencies. This double perspective gives some keys to understand the threats of our « dark times ».
Economics
Keywords: ARENDT; Hannah; economic liberalism; mass society

The Making of Karl Polanyi's Economic Sociology. (In Japanese. With English summary.) - Wakamori, Midori (History of Economic Thought, 2010)
The main purpose of this paper is to understand Polanyi's research project after The Great Transformation. This includes his developing ideas on economic history and theory of economic institutions after 1947, when he came to Columbia University in New York. This paper deals mainly with Polanyi's new agenda, namely "the place of the economy in society" in the intellectual context of post World War II United States of America.
Economics; Sociology
Keywords: Marxist; Sraffian; economic anthropology; economic sociology; history of economic thought since 1925: socialist; history of economic thought: individuals; social and economic stratification

Karl Polanyi, Athens and us: the contemporary significance of Polanyi's thought - Wjuniski, Bernardo Stuhlberger; Fernandez, Ramón G. (Revista de Economia Política, 2010)
Karl Polanyi is considered one of the most prominent social scientists of the 20th century. In his writings, an important concern was the relationship between the markets and the society (therefore, the state) as a whole; to discuss it, he introduced the concept of "embeddedness", fundamental for his study of the origins and consequences of the Industrial Revolution. An important part of his heritage is the study of the economic history of what he called "ancient societies," especially of Classical Greece. Polanyi used these studies to compare the ancient societies with his own times, in an effort to understand them all. This paper aims to relate Polanyi's work on the Athenian society with his studies about the modern times, showing that it is possible to draw lessons from Polanyi's thought on the relationship between the society, the state and the market that can help to design a political agenda for our days. In the first part, we present the most important aspects o the life and work of Polanyi, and in the second we discuss the most important aspects of his worldview. Then, in the third part, we study his view of the early Athenian economy; mainly, we focus on the coexistence of a kind of state planning and a market, showing how this understanding is crucial for the whole Polanyian legacy, with its emphasis in the comparison of different societies and times. We conclude by underlining the relevance of this interpretation advanced by Polanyi to understand the societies of our days, focusing on some proposals to extend his approach to deal with our contemporary problems.
History; Economics
Keywords: classical Greek economy; economic history; embeddedness

The Rise and Fall of the Market Economy - Zaman, Asad (Review of Islamic Economics, 2010)
The core economic functions of production and distribution of goods can be handled by many different methods. After the fall of communism, the market mechanism has become nearly universal. Conventional economic theories argue that this is natural, because it is the best and the most efficient method for organizing economic affairs in a society. This paper, based on the analysis of Polanyi (1944) and Klein (2008) argues that the opposite is true. Market mechanisms conflict with natural mechanisms for production and exchange in traditional societies. Unregulated markets cause tremendous damage, as can be witnessed today in terms of countless economic crises, wars, environmental destruction, as well as damage to social networks. Because of this damage, market societies can only be maintained by force, as well as disinformation. To resolve crises on myriad fronts caused by the unregulated market, it is the need of the hour to find viable alternatives.
Economics
Keywords: capitalist systems: performance and prospects; comparative analysis of economic systems; cultural economics: religion; other economic systems: performance and prospects

The Role of the State in Making a National Market: The Evolution of the Grain Market in China (1978-2000) - Zhou, Wubiao (China Agricultural Economic Review, 2010)
The paper aims to examine Karl Polanyi's view of market evolution in the context of the emergence of a national grain market in China's transition economy. The dataset used includes information about inter-provincial grain trade on China's grain market from November 1999 to October 2000. A priori blockmodelling method is used for hypothesis testing. This paper finds that a partially integrated national grain market had emerged at the beginning of the twenty-first century in China in spite of local protectionism. Additionally, the emergence of this market is found to be partly a result of the reform-oriented state's attempt to create national wholesale grain markets.
Economics; Sociology
Keywords: agricultural policy; agriculture; agriculture: aggregate supply and demand analysis; collectives; communes; economic development: agriculture; energy; environment; food policy; natural resources; other primary products; prices

Managing Liberalization and Globalization in Rural China: Trends in Rural Labour Allocation, Income and Inequality - Dong, Xiao-Yuan; Bowles, Paul; Chang, Hongqin (Global Labour Journal, 2009)
China’s integration into the global economy, while rapid, has been managed as part of a wider liberalization process. The structural changes in the rural economy arising from these twin processes have led to widening intra-rural inequalities. To address these, the central leadership has, in Polanyian manner, moved to counter some of the adverse effects of liberalization and globalization. We discuss this dynamic as it has affected rural China. We analyze results from a national data set covering the period 1991-2006 to assess the extent to which the state has been successful in protecting society from the advance of market forces. We find positive outcomes in terms of real earnings growth and poverty reduction but negative outcomes in terms of the rise in open unemployment and in terms of increasing intra-rural income inequality, although this was noticeably more pronounced in the 1991-2000 period than in the 2000-2006 period when more active government redistributive mechanisms were in place.
Economics
Keywords: globalization; income inequality; labor studies; labour allocation; labour studies; liberalization; rural China

L’« institution » selon Karl Polanyi. Fondements et mise en perspective contemporaine - Maucourant, Jérôme; Plociniczak, Sébastien (Tracés. Revue de Sciences humaines, 2009)
Depuis les années soixante-dix, certains économistes ont tenté de répondre aux difficultés de plus en plus nombreuses qu’ils rencontraient en réélaborant le concept d’institution. Cette tentative « néo-institutionnaliste » fut porteuse de malentendus. L’autonomisation progressive de l’économie comme savoir s’était, en effet, construite sur l’occultation délibérée de toutes sortes de fondements extra-économiques. La quête de tels fondements, dans l’intention d’asseoir scientifiquement la conna...
Economics
Keywords: MALTHUS; T. R.; RICARDO; David; institutionalist approach

The Athenian Economy in Light of the Welfare State: Karl Polanyi's Work in Perspective - Wjuniski, Bernardo Stuhlberger; Fernández, Ramón García (Journal of Economic Issues (Taylor & Francis Ltd), 2009)
Karl Polanyi considered that the relationship between the markets and their societies was a central feature of any social order. He studied what he called "ancient societies," to compare them with his own times, in an effort to understand that subject This paper aims to show, following Polanyi's work on Classical Greece, that it is possible to make a clear analogy between the Athenian state and economy with the modern Welfare State. First, we present Polanyi's study of the early Athenian economy, focusing on the coexistence of a kind of state economic planning and a market Second, we show how this relates to Polanyi's emphasis in the comparison of different societies and times. Third, we characterize the contemporary Welfare State to make an analogy between these two forms of economic organization. We conclude by underlining the relevance of this analogy in understanding the societies of today.
Economics; Anthropology
Keywords: Athenian supremacy; Greece; 479-431 B.C.; Athens (Greece) - history; Greece; Polis (the Greek word); classical Greek economy; economic anthropology; economic policy; embeddedness; equity; history of economics - to 1800; imperialism; markets - social aspects; money; social order; welfare state

Relaxing the shackles: The invisible pendulum - Stewart, Frances (Journal of International Development, 2009)
This note draws on Polanyi's pendulum in economic policies presented in the the Great Transformation—with swings back and forth between strong restrictions on the market and market domination, each resulting from excesses of the dominant model. The swing he described, when he wrote, was a reaction to the consequences of market domination, notably the Great Depression, and ushered in Keynesianism and the welfare state. In the late twentieth century, there was a swing back towards the market as a result of the inefficiencies associated with this interventionism. This note argues that the pendulum is swinging again, following the political and economic consequences of this market domination. Again market forces are being restrained by regulation, state takeovers, social protection and Keynesian macro-policies, while environmental factors have added to pressures for interventionist policies. Copyright © 2009 John Wiley & Sons, Ltd.
Development Studies; Economics
Keywords: Polanyi; interventionism; markets; pendulum

Le differenti ibridazioni di risorse nelle imprese sociali europee - Gardin, Laurent (The various types of resources mobilised by European social enterprises., 2009)
The objective of this paper is to analyse, on the basis of the substantive definition of the economy (elaborated in the footsteps of Polanyi), the various types of resources mobilised by European social enterprises. European social enterprises use a complex mix of resources based on four types of economic relations: the market, redistribution, the socio-politically embedded market, and the reciprocity. A European typology of Work Integration Social Enterprise (WISEs) is put forward, in order to understand these enterprises' dynamic across national borders. (English)
Sociology; Economics
Keywords: Europe; business enterprises; distribution; economic theory; markets; reciprocity (commerce); social enterprise; socioeconomics

Paper assets, real debts: An ecological‐economic exploration of the global economic crisis - Kallis, Giorgos; Martinez‐Alier, Joan; Norgaard, Richard B. (Critical perspectives on international business, 2009)
Purpose – This paper sets out to investigate the potential contribution of the inter‐disciplinary field of ecological economics to the explanation of the current economic crisis. The root of the crisis is the growing disjuncture between the real economy of production and the paper economy of finance. Design/methodology/approach – The authors trace the epistemological origins of this disjuncture to the myths of economism – a mix of academic, popular and political beliefs that served to explain, rationalise and perpetuate the current economic system. Findings – The authors recommend ending with economism and developing new collective and discursive processes for understanding and engaging with ecological‐economic systems. Originality/value – The authors embrace the notion of sustainable de‐growth: an equitable and democratic transition to a smaller economy with less production and consumption.
Economics; Business
Keywords: commodification; commodification of nature

An Introduction to Destructive Coordination - Vahabi, Mehrdad (American Journal of Economics and Sociology, 2009)
Polanyi (1944, [1957]1968) has distinguished three “patterns of social integration,” namely, “reciprocity,”“redistribution,” and “exchange.” This triad has provided the starting point for most subsequent discussion. Our purpose is to introduce a further type of coordination, the “destructive mode of coordination.” This mode achieves coordination by intimidation, threat, and the use of non-institutionalized coercive means. Resources and human efforts are allocated in order to appropriate what other people produce. Two simple examples provide an introductory illustration: traffic circles (roundabouts) and prisons. Appropriation through pirating provides a further example of destructive coordination. More specifically, biopiracy (blood patenting) is discussed in order to clarify the relationship between destructive coordination and the institutionalization of property rights. Finally, we focus on the role of destructive coordination as a transitional mechanism that is supported by the institutional vacuum, ultimately yielding to other modes of coordination.
Economics; Sociology
Keywords: appropriation; destructive mode of coordination; social integration

The Social Economics of Neoliberal Globalization - Stanfield, James Ronald; Carroll, Michael C. (Forum for Social Economics, 2009)
The recent period of intensive and extensive development of global economic integration, or globalization, has reached a crossroads. The regime of the neoliberal Great Capitalist Restoration is not sustainable and fundamental governance changes must be made. This paper adds perspective to the choices that must be made at this critical juncture of the global social economy by applying the master concepts of Schumpeter's Creative Destruction and Polanyi's Protective Response.
Economics
Keywords: capitalist systems: political economy; global social economy; international economic order; protective response; social economy

Karl Polanyi et La Pédagogie De L'incohérence - Gazier, Bernard; Mendell, Margie (Annals of Public and Cooperative Economics, 2009)
Cet article vise à examiner de manière critique et constructive l'actualité de la pensée de Karl Polanyi pour comprendre le développement de l'économie plurielle au XXIe siècle et pour agir sur celui-ci. Il montre la très grande actualité de cette pensée, ainsi que la nécessité de s'intéresser à l'œuvre entière de Karl Polanyi, et pas seulement à«La grande transformation». Partant des usages multiples du concept d'encastrement et de désencastrement, il relie les propositions inspirées par Karl Polanyi sur «le processus institué de démocratisation économique»à des développements récents tant pratiques que théoriques: les «>marchés transitionnels du travail» et la «nouvelle finance publique». ENG: The aim of this article is to examine critically and constructively the current state of Karl Polanyi's thinking in order to understand and act on the development of the pluralist economy in the twenty-first century. It shows the very topicality of this thought, as well as the need to take an interest in the entire work of Karl Polanyi, not just "The great transformation". Starting from the multiple uses of the concept of embedding and disencing, he links the proposals inspired by Karl Polanyi on "the instituted process of economic democratization" to recent practical and theoretical developments: "transitional labor markets" and " New public finance ".
Economics
Keywords: economic democratization; instituted economic process; new public finance; pluralist economy; transitional labor markets; transitional labour markets

Keynes’s Stimulus, Polanyi’s Movement - Milberg, William S. (Harvard College Economic Review, 2009)
The foundations of Keynes and the principles of Polanyi offer insight into crafting a new American economy
Economics
Keywords: KEYNES; John Maynard; 1883-1946; economics

Second thoughts: on economics, sociology, neoliberalism, Polanyi's double movement and intellectual vacuums - Piore, Michael J. (Socio-Economic Review;2009, Vol. 7 Issue 1, p161, 2009)
The article presents a presidential address by Michael J. Piore, delivered at the Society for the Advancement of Socio-Economics (SASE) Annual Meeting 2008 in San José, Costa Rica, in which he discussed the relationship between sociology and economics, and the role that this relationship plays at the current political juncture in the transition from neoliberalism to the formation of public policy.
Sociology; Economics
Keywords: double movement; economic sociology; neoliberalism

Endogenous Institutions and the Politics of Property: Comparing and Contrasting Douglass North and Karl Polanyi in the Case of Finance - Davis, Ann E. (Journal of Economic Issues, 2008)
The purpose of this paper is to contrast the work of Douglass North and Karl Polanyi regarding financial institutions associated in market economies. Both implicitly acknowledge the synergy between public and private financial markets, which can serve to solidify an alliance between wealth holders and the state, potentially at the expense of “sociery” at large. This alliance may stimulate growth, according to North, as well as impose the strain of the market, according to Polanyi. Taken together, these insights undercut the classical story of the neutral role of money, as well as the notion of a clear distinction between public and private, politics and markets.
Economics
Keywords: NORTH; Douglass; economic history; finance; property

Encastrement et nouvelle sociologie économique : de Granovetter à Polanyi et Mauss - Laville, Jean-Louis (Revue Interventions économiques. Papers in Political Economy, 2008)
Le concept d’encastrement s’est imposé dans la nouvelle sociologie économique. Ce texte souligne sa polysémie. Dans une première partie, il rappelle les deux acceptions politique et réticulaire respectivement adoptées par Granovetter et Polanyi. Rapportée à la modernité démocratique, la démarche de Polanyi permet de mettre en évidence un double mouvement caractérisant les rapports entre économie et société, dont les grands traits sont synthétisés dans la deuxième partie. Si l’on adopte une telle lecture, la convergence entre Polanyi et Mauss apparaît alors dans une approche plurielle de l’économie, présentée dans la troisième partie. Selon l’hypothèse esquissée dans la quatrième partie, une telle lecture suggère d’approfondir la teneur des changements institutionnels susceptibles de conforter la pluralité de l’économie, autrement dit de participer à son « ré-encastrement » démocratique. The concept of embeddedness has imposed itself in the New Economic Sociology. This paper highlights the multiple meanings of this term. In a first part, we discuss the political and reticular meanings adopted by Granovetter and Polanyi respectively. In the context of modern democracy, the work of Polanyi shows a double movement characterizing the relations between economy and society, which we develop in the second part. With such a perspective, the convergence between Polanyi and Mauss is highlighted in a plurial approach of the economy, which we discuss in the third part. The hypothesis presented in the fourth part leads us to analyze the content of institutional changes which can confirm the plurality of the economy, and to participate in its democratic « reembeddedness ».
Sociology; Economics
Keywords: GRANOVETTER; Mark; MAUSS; Marcel; 1872-1950; economic sociology; encastrement; niveau d’intégration; sociologie économique

Le capital et la question nationale - Maucourant, Jérôme; Tinel, Bruno (Actuel Marx, 2008)
Nations are the forms of political organization which peoples construct for themselves. It is a commonplace to state that globalization tends (for the better) towards the end of nations. However the history of capitalism shows that such a hypothesis is questionable. Globalization is merely a stage in the development of capitalism, which has always leaned on certain nations to secure its deployment: England in the past, the U.S. today. The real question is thus that of the hegemony of one nation over other nations and, ultimately, the question of democracy, the sovereignty of peoples in the face of capital.
Economics
Keywords: democracy; globalization

Rationality as a Social Construction: What Does Individual Behavior Have To Say About Development in an Amazon Community? - Gramajo, Andrés Marroquín (Journal of Economic Issues (Association for Evolutionary Economics), 2008)
This article argues that two different manifestations of rational behavior can coexist and collide in a relatively homogeneous society. In the Ticuna community of Arara in the Colombian Amazon; on the one hand, the majority of villagers tend to reach relatively lower levels of material wealth, following Polanyi's idea of the pre-modern man (1968a; 1968b; 1968c), and also Sahlins' (1972) idea of the original affluent man. On the other hand, community leaders and schoolteachers tend to accumulate material wealth, following Polanyi's idea of modern-man (1968a; 1968b). These behavioral frameworks help explain the limited success of certain types of development programs in the Ticuna community.
Economics
Keywords: Amazon River Region; Colombia; Tucuna (South American people); behavioral economics; communication in economic development; economic development; economic policy; economics - moral & ethical aspects; pre-modern man; rationality; reason; saving and investment; statics & dynamics (social sciences); wealth

Karl Polanyi's and Karl William Kapp's Substantive Economics: Important Insights from the Kapp—Polanyi Correspondence - Berger, Sebastian (Review of Social Economy, 2008)
Based on the unpublished Kapp-Polanyi correspondence, the paper analyzes the relationship between the two economists, as well as the meaning and origin of substantive economics, i.e. one of the key concepts of institutional economics with distinctly European roots. The correspondence shows how both economists influenced each other in their similar understanding of the substantive economy, and reveals that these similarities and the mutual influence date back to the 'planning debate' of the 1920s and 1930s. The documents also evidence the importance of Carl Menger's definition of substantive economics in the posthumous and untranslated second edition of the Grundsätze der Volkswirtschaftslehre (Principles of Economics) (1923). As a result, Kapp's political economy, i.e. his social minima approach appears in new light. The latter actualizes the full potential of substantive economics for a modern political economy by integrating insights from Polanyi's substantive economics, Menger's differentiation of human needs according to their urgency, and Max Weber's substantive rationality.
Economics
Keywords: KAPP; Karl William; environmental management; social economy; substantive economics

Transformations, Then and Now: The Appeal of Karl Polanyi - Karnik, Ajit (Economic and Political Weekly, 2008)
Karl Polanyi's views on the nature of "pre-market" society are influential not only among historians but also among economists concerned with present-day transitional and developing economies. This paper examines Polanyi's arguments about the "Great Transformation" from traditional to market society in the light of recent advances in economic theory and empirical evidence from a range of European and non-European societies. These theoretical and empirical considerations provide little support for Polanyi's views concerning fundamental discontinuities between traditional and market societies. The paper concludes that Polanyi's rosy view of pre-market society provides an inappropriate historical basis for addressing the challenges faced by present-day transitional and developing economies.
Economics
Keywords: critique; economic history; market economies; market economy; market mechanism; market mechanisms; money; peasant class; pre-market society; transitional economies

KARL POLANYI ABOUT INSTITUTED PROCESS OF ECONOMIC DEMOCRATIZATION AND SOCIAL LEARNING - Mendell, Marguerite (PEKEA Newsletter N° 14, April – June 2008 / ResearchGate, 2008)
This text will not focus on The Great Transformation but will deal with previous and following writings from Karl Polanyi where his emphasis is on the constitutive elements that define us as social beings and as agents of social change.
Economics; Political Science
Keywords: Great Transformation; The (Book); economic democratization; education; instituted economic process; social learning

Economie et Rationalite: Apports et limites de l'approche polanyienne. (Economics and Rationality: Contributions and Limits of Polanyian Approach. With English summary.) - Postel, Nicola; Sobel, Richard (Cahiers d'Economie Politique, 2008)
Polanyi analyzes the historical deployment of a "formal" economic science starting from the triptych "market-rarety-instrumental rationality". It reveals this triptych, and the knowledge which is devoted to it, as being a part of a question broader than should analyze a "substantial" economic science being interested in the triptych "need-nature-institution". If we can and must follow Polanyi in his criticism of economism suited to the first triptytic, we have more reserve to accept his solution of substitution, an heterogeneous mixture of naturalism and institutionalism, of essentialism and historicism. The thesis defended in the article is that it is necessary to be more Polanyian that Polanyi himself, and to develop an economy of the practical reason, base of an economic science reintroduced inside social sciences.
Sociology; Economics
Keywords: criticism of economism; formal economy; general economics

Karl Polanyi and Return of the "Primitive" in Institutional Economics - Özveren, Eyüp (Journal of Economic Issues (Association for Evolutionary Economics), 2007)
This article discusses a renewed interest in the work of scholar Karl Polanyi and the incorporation of his work into the body of institutional economics. This article discusses the notion of time in Polanyi's work and how it differs from the metaphor of time inherent in neoclassical economics. The author discusses the definition of the word "primitives" and its relationship to social policy, and how Polanyi deployed the actual state of primitives in order to replace the economistic cost-benefit analysis of the Industrial Revolution with a "social cost" alternative.
Economics
Keywords: POLANYI; Karl; 1886-1964; corporate culture; cost effectiveness; externalities; externalities (economics); industrial psychology; industrial revolution; institutional economics; social policy; social psychology

Policymaking and Learning Actors, or Is A 'Double Movement' In Cognition Possible? - Ramazzotti, Paolo (Journal of Economic Issues (Association for Evolutionary Economics), 2007)
This article discusses the relationship among economic constraints, social reform and societal pressures for a humane society, drawing on the insights of scholars Karl Polanyi and Herbert A. Simon. One of the key issues in Polanyi's work is the divergence between economic and societal values in modern capitalism. The divergence leads to a reaction against the rationale of the market and to what Polanyi refers to as the double movement. The distinction between internal consistency and external consistency is described to frame the role of institutions in the economy.
Economics
Keywords: POLANYI; Karl; 1886-1964; SIMON; Herbert A.; 1916-2001; capitalism; double movement; economic policy; economic sectors; evolutionary economics; markets - social aspects; socioeconomic factors; socioeconomics

Karl Polanyi and the Modernity-versus-Postmodernity Debate - Özveren, Eyüp (European Legacy, 2007)
The originality of Karl Polanyi's (1886-1964) work in the interwar period and his work in the 1950's has gained increasing recognition in recent years, during which time the major debate on modernity has erupted. In order to link Polanyi's work with this debate, the article first discusses his legacy on the controversial concept of progress and then relates his position to this debate. Polanyi's position combines the better aspects of the two rival approaches to modernity. The article then relinks Polanyi's thought to the intellectual figures, movements, and climate of his time and thereby discloses a curious affinity between his thought and the critical theory of the Frankfurt School. This affinity can best be understood within the parameters of the historical context that they once shared.
Economics
Keywords: POLANYI; Karl; 1886-1964; debates and debating; economics; modern society; modernity; postmodernism (philosophy); progress

La connaissance, une marchandise fictive, Knowledge, a Fictitious Commodity - Azam, Geneviève (Revue du MAUSS, 2007)
Cet article se propose d’analyser le sens de l’invention d’une « économie de la connaissance » et de la transformation de la connaissance en bien économique, illustrée par la transformation des droits de propriété intellectuelle. En poursuivant l’analyse de Karl Polanyi à propos des « quasi-marchandises », la connaissance doit plutôt être considérée comme une marchandise « fictive ». C’est le point de vue adopté dans cet article qui montre comment la tentative actuelle de rendre cette fiction effective menace la connaissance elle-même en l’assignant à un rôle instrumental., This article offers some reflections on the sense given to the invention of a « knowledge economy » and on the conditions of knowledge commodification, as illustrated by the current changes in knowledge property rights. Elaborating on Karl Polyani’s argument about « quasi-commodities », we have to regard knowledge as a « fictitious commodity » rather than a simple commodity. It is the point of view we have adopted in this article, which shows that the current attempts at giving this fiction more actuality pose a threat to knowledge itself by confining it to an instrumental function.
Economics
Keywords: fictitious commodities; knowledge

The Early Debate on Economic Calculation in Vienna (1919-1925): The Heterodox Point of View: Neurath, Mises and Polanyi - Becchio, Giandomenica (Storia del Pensiero Economico: Nuova Serie, 2007)
This paper is based on the idea that the early debate on economic calculation in a planned economy conducted in Vienna among Neurath, Mises, and Polanyi (1919-1925) was the starting point for the development of a particular form of heterodox economic theory propounded by liberal thinkers like Mises and by socialists like Neurath and Polanyi. Mises claimed that solving the problem of calculation was impossible, and consequently that a centrally planned economy was not theoretically feasible. Neurath and Polanyi instead sought to solve the problem of calculation and, despite certain profound differences between their views, they proposed a socialistic model alternative to the orthodox Marxist one.
Economics
Keywords: MISES; Ludwig von; Marxism; NEURATH; Otto; economic calculation; economic thought; heterodox economic theory; heterodox economics; history of economic thought; history of economics; planned economy

Non-Trade Concerns in Agricultural and Environmental Economics: How J.R. Commons and Karl Polanyi Can Help Us - Barthélemy, Denis; Nieddu, Martino (Journal of Economic Issues, 2007)
Economics
Keywords: COMMONS; J.R.; economics; environmental economics; substantive economy

Philosophizing with a hammer? A critique of Mirowski's markomata informed by continental philosophy - Juniper, James (Journal of Economic Behavior & Organization, 2007)
Abstract: Mirowski''s justification for replacing the foundational principles of neoclassical economics – methodological individualism and rational choice theory – with a theoretical framework informed by cybernetics, information theory, and computational biology, is subject to a critique informed by the work of Karl Polanyi, Michel Foucault and Jürgen Habermas. Mirowski''s proposed alterative is called into question on the basis of two crucial weaknesses. First there is Mirowksi''s penchant for what Polanyi has called Laplacian reductionism. Second there is Mirowski''s inability to develop a comprehensive and consistent theory of evolutionary economics. Mirowski''s work is questioned in terms of what social theorists call the ‘structuration paradox’.
Economics
Keywords: FOUCAULT; Michel; 1926-1984; MIROWSKI; Philip; continental philosophy; cybernetics; economic methodology; economics; social theory; structuration paradox

Principles of Institutional-Evolutionary Political Economy – Converging Themes from the Schools of Heterodoxy - O'Hara, Phillip Anthony (Journal of Economic Issues (Association for Evolutionary Economics), 2007)
The article examines the renewed interest in heterodox political economy. Institutionalists, post Keynesians, neo-Marxists, and feminists among others, and various sub-groups provide schools of thought on heterodoxy. The guidelines of institutional-evolutionary political economy (IEPE) are offered alongside socioeconomic analysis and complexity theories. The author outlines the conflict of individual v. structure. Other topics covered include social capital, heterogeneous agents, financial instability, cumulative causation, institutional environments, community and governance, and destructive creation.
Economics
Keywords: Keynesian economics; creative destruction; disembedded economy; economic policy; evolutionary economics; heterodox economics; heterodox political economy; infrastructure (economics); mixed ability grouping (education); political economic analysis; social capital; social theory

Le « Gas Argentine » Revisite: De L'utopie Libérale Au Retour De La Politique… - Blaum, Luis (El «caso argentina» revisitado. De la utopía liberal al regreso de la potítica…., 2007)
Argentina constitutes a revealing textbook case of the link between the liberal utopia of an auto-regulated market, commodity fetishism and economists' theories. How does economic liberalisation, backed by a law on currency convertibility, resolve the crisis of political representation affecting the country since the emergence of Peronism, the «voice of the voiceless», in the 1940s? The liberal utopia of markets' auto-regulation associates taking root in social life with having money, by means of what Marx called the «vulgar economy». From this viewpoint, the monetary crisis of 2001, a real social tragedy, illustrates Polanyi's thesis: liberal utopia's stumbling blocks force societies to give markets roots which have political and social dimensions. But, conveyed by economic thought, commodity fetishism continues to play an active role in exiting a crisis. The political position is perilous and based on a scientific approach that makes people believe that social reality can be completely manipulated. (English)
Economics
Keywords: Argentina; MARX; Karl; 1818-1883; commodity fetishism; financial crises; financial crisis; utopia

Le marché, une institution entre économie et histoire - Maucourant, Jérôme (Cahiers lillois d'économie et de sociologie, 2007)
"L'hypothèse de l'article est la suivante : il n'est pas possible de parler rigoureusement d'un concept de « marché » en science économique, car ce concept est en réalité une notion floue, au mieux ambivalente. En revanche, le recours à d'autres sciences sociales, comme l'histoire et la sociologie, peuvent aider à la construction d'un concept de marché. Ainsi, le travail de Karl Polanyi et les travaux d'historiens contemporains, notamment ceux d'Alain Guéry, semblent utiles pour mieux distinguer le marché propre à la « société de marché » au sens de Polanyi des marchés caractéristiques des économies archaïques ou d'Ancien régime. L'histoire des idées et la réhabilitation du travail de Montchrestien, contre le jugement hâtif de Schumpeter, est mobilisée pour illustrer l'hypothèse de l'article. Il est enfin suggéré que ni l'approche en terme d'équilibre général, ni les travaux d'Israël Kirzner n'ont eu de valeur heuristique en ce qui concerne la présente problématique." ENG translation: "The topic of the paper consists in arguing that it is not yet possible to have a rigourous concept of « market », as so far as economics is concerned. Nor equilibrilim theory nor kirznerian approach have a real interest for the precise task of conceptualising market as such. At best, « market » is a undetermined notion or, in some case, has even a double meaning (market place and selfregulating market). Nevertheless, thanks to other social science, i.e. history and sociology, il is possible to elaborate a concept of market. Works of Karl Polanyi, but also more recent contributions of a historian of french Ancien Régime economy, Alain Guéry, are usefull from this point of view. Then, a clear distinction seems to be done between market of modern « market society ». The paper insists also in giving ti the Montchrestien Traicté de l'Œconomie politique a importance denied by Schumpeter. "
Economics; Sociology
Keywords: economic theory; markets

On the need for a heterodox health economics - McMaster, Robert (post-autistic economics review, 2007)
INTRO: This paper is a plea for greater cognizance of the errors of omission and commission committed by mainstream health economics, and the potential orientation in treating health and health care as (metaphorical) commodities that the unfettered influence of health economics may be prompting. Economic criticisms of mainstream health economics are evident, especially in the collection edited by John Davis (2001), but tend to be rather fragmented and lacking in credibility with our mainstream brethren. Contentiously, seeking the approval or otherwise of the mainstream is perhaps not as important as in other areas of economics, if indeed it is the case at all, but gaining the attention of other social scientists, medics, and policy makers may be of considerable consequence. The paper does not seek to speculate on strategies for addressing these bodies; instead it concentrates on the nature of the message.
Economics
Keywords: commodity fiction; fictitious commodities; health; health economics; political economy

Karl Polanyi et le processus institué de démocratisation politique, Karl Polanyi and the Instituted Process of Political Democratization - Mendell, Marguerite (Revue du MAUSS, 2007)
Cet article porte sur le « processus économique institué » de Karl Polanyi. Il s’appuie sur certains de ses écrits moins connus, qui précèdent et suivent la publication en anglais de la Grande Transformation, dans lesquels Polanyi insistait en particulier sur la capacité des individus et des collectivités à agir sur leur propre destinée. Ces écrits nous aident à conceptualiser les processus de transformation institutionnelle qui caractérisent la société contemporaine. Cet article s’intéresse à l’impact de la société dite civile sur l’innovation en matière de politiques ou d’institutions, sur les préconditions qui institutionnalisent, pour ainsi dire, ces pratiques – qui se transmettent ensuite horizontalement aux sous-systèmes institutionnels et verticalement aux institutions macro ou gouvernantes. ENG: This article bears on Polanyi’s « instituted economic process » and uses a range of not very well known articles published before and after The Great Transformation where Polanyi insisted on the capacity of individuals and communities to shape their own destiny. Here we are particularly interested in the impact of civil society on political innovation which percolates both along horizontal or vertical lines.
Economics; Sociology
Keywords: instituted economic process

Au-delà d'une certaine lecture standard DE La Grande Transformation - Plociniczak, Sébastien (Revue du MAUSS, 2007)
Whereas a largely conveyed standard reading of The Great Transformation lets one think that Karl Polanyi establishes the effective birth certificate of a self-regulated market at the nineteenth century in the West, this text suggests that The Great Transformation makes Polanyi the author of a criticism of the theoretical fiction of the self-regulated market, and the historian of this acting fiction which directs individual behaviors and transforms in-depth the Western societies of the nineteenth century.
Economics
Keywords: Great Transformation; The (Book); great transformation; reinterpretation

Redistribution and Markets in the Economy of Ancient Mesopotamia: Updating Polanyi - Silver, Morris (Antiguo Oriente, 2007)
Economics
Keywords: capital formation; damkar/tamkaru; demand/supply curve; equivalence; redistribution

On markets and morality: Revisiting Fred Hirsch - Carvalho, Luís Francisco; Rodrigues, João (Review of Social Economy, 2006)
This article argues for the continuing relevance of Fred Hirsch's The Social Limits to Growth (1976), valued as a critical analysis of the consequences of markets on the moral fabric of society. Two concepts that are fundamental to Hirsch—the commercialization bias and the depleting moral legacy—will be scrutinised. We further claim that this book, by emphasizing the tendency to market expansion and the corresponding commodification of increasing spheres of social life, while simultaneously acknowledging its adverse consequences on the motivational appeal of social and moral norms, offers insights that justify revisiting it.
Economics
Keywords: HIRSCH; Fred; double movement; markets; morality; neoliberalism; second great transformation; social economy

L'utopie de l'économie de la connaissance - Azam, Geneviève (Problèmes économiques n. 2901, 2006)
"L'expression "économie de la connaissance" a, en ce début du XXIe siècle définitivement remplacé celle, très en vogue à la fin des années 1990, de "nouvelle économie". Les sociétés les plus avancées auraient désormais atteint un nouveau stade du développement économique dont la connaissance serait le facteur essentiel. Cette idée laisse supposer que jusque-là, celle-ci ne jouait qu'un rôle secondaire dans le processus productif. L'auteur se propose d'expliquer le sens et les implications que ce nouveau statut confère au savoir et à la recherche. Pour mieux comprendre ce qui est à l'oeuvre avec l'invention d'une "économie de la connaissance", elle analyse tout d'abord, à travers l'évolution récente des droits de propriété intellectuelle, les conditions de la transformation de la connaissance en bien économique. S'appuyant sur les travaux de Karl Polanyi, à propos des "quasi-marchandises", l'auteur montre ensuite qu'en réalité celle-ci est une marchandise "fictive" et que la tentative actuelle de lui assigner un rôle instrumental constitue pour elle-même une grave menace." ENG: Building on the work of theKarl Polanyi , on the subject of "quasi-merchandise", the author then shows that, in reality, the latter is a "fictitious" commodity and that the current attempt to assign to it an instrumental role constitutes for itself a serious threat
Economics
Keywords: Lisbon Strategy; biodiversity; economic property; economy of knowledge; ethics; evaluation; intangible assets; intellectual property; patents

Is There an Opportunity to Establish the Social-Capitalism in the Post Socialist Transition? - Losonc, Alpar (Panoeconomicus, 2006)
Recently Claus Offe has put the question that concerns the fate of the European model of social capitalism: can the model of social capitalism survive the European integration in the context of certain contemporary tendencies? Offe has presupposed that the mentioned model is challenged by the processes of globalisation and the integration of the post socialist countries into the European Union. The working hypothesis of the article is that there is an opportunity to provide a coherent answer to this question. The article consists of two parts. In the first part the author starts with the Polanyi's socio-economic theory and emphasises the importance of this approach for the analysing of the tendencies of capitalism in Western Europe and in the post socialist countries. The author argues that with the Polanyi's theory we are able to explicate the forms of the embedded liberalism in Western Europe after 1945 and the orientation of non-embedded neo-liberalism and the functioning of the workfare state after the crisis of the Keynesian welfare state. Despite the tendencies of the globalisation projected by neo-liberalism, the central element of the social capitalism, namely, the welfare state, remains with the dimensions of the continuity. In the next part the author points out that there is an asymmetrical structure between the Western-Europe and non-Western part of Europe concerning the socialisation of capitalism. The neoliberalisation in accordance with the model of the transfer of ideal-type of capitalism is more strongly implemented in the countries of transition. In addition, the mentioned theoretical approach provides opportunities to explain the failures of implementing of neo-liberalism in the post socialist countries. On the basis of the endorsing of the socio-economic aspects we can address the issue pointed out by Offe.
Economics
Keywords: consumer economics; education and training; health; poverty; property rights; provision and effects of welfare programs; social security and public pensions; socialist institutions and their transitions; socialist systems and transitional economies: political economy; welfare; well-being; and poverty: government programs

Commercialisation, inequality and the limits to transition in health care: a Polanyian framework for policy analysis - Mackintosh, Maureen (Journal of International Development, 2006)
The effects of commercialised health care in embedding, exacerbating and legitimating social and economic inequality are at the root of widespread and recurrent resistance to commercialisation in health. In low income developing countries suffering generalised poverty, and notably in Sub-Saharan Africa, liberalisation of largely unregulated clinical provision has created a substantially informalised, fee-for-service primary health sector which is exclusionary, low quality and under stress. This article argues against a policy assumption that health systems constitute a sector that can benefit like other commodities from liberalisation. Health care is better understood as a ‘fictional commodity’ in the Polanyian sense: inappropriate for full commodification, producing intensely perverse effects when provided on competitive markets, and therefore requiring planning and social constraint. If managed effectively, integrated health systems—like redistributive land reform and effective labour protection—can support a broader economic transition that avoids extremes of inequality; conversely if treated simply as a transitional sector, health systems can make exclusion and inequality much worse. Copyright © 2006 John Wiley & Sons, Ltd.
Economics; Political Science
Keywords: Africa; Sub-Saharan; economic structure; equality; health care reform; liberalism; medical care; medical policy

An institutionalist perspective on the future of the capitalist world-economy - Özçelik, Emre; Özveren, Eyüp (Journal of Economic Issues, 2006)
The term world-economy in our title must have already given a hint to the careful reader of our purpose in writing this paper: We intend to bridge institutional economics with world-systems analysis in order to enhance the global applicability of the former. World-economy is a term used by Fernand Braudel and Immanuel Wallerstein and means a space defined by the existence of a single division of labor (coexistent with multiple States) whereas world economy would indicate the arithmetic summation of national economies each of which ... In this paper, we elaborate Polanyi's concept of embeddedness so as to construct an institutionalist framework to understand the contemporary world-economy. We contend that embeddedness can be deployed to analyze the so-called "global governance model" (GGM) as the most recent liberal recipe.
Economics
Keywords: embeddedness; global governance model; world-economy

The Market, Mind and Rationality. From Vienna to Paris and Back - Rotstein, Abraham (Revue européenne des sciences sociales, 2006)
The mention of the great city of Vienna conjures up the many legacies of music, art and philosophy which it nurtured. But as important as any of these is the more prosaic legacy of the Austrian economists ranging from C. Menger to F. von Hayek. And for some, Vienna may conjure up as well, the debate that K. Polanyi had with these economists in the 1920s. However paradoxical it may seem, it was by virtue of this debate, carried on directly and indirectly over a lifetime, that Polanyi was first and foremost an Austrian, or rather an Austrian «in mirror image ». This was true not only by virtue of the years of his life and his work in Vienna, but more so because he was drawn into and remained a protagonist in the debate around the fundamental issues first raised by the Austrian economists. Menger and his followers E. von Bohm-Bawerk, and L. von Mises had established and diligently pursued much of the agenda of the debate. F. von Hayek was the important representative of this school in recent decades. The particular topic launched by von Mises in 1920 was whether a socialist economy was at all viable without the direction provided by market prices. Regulated or administered prices were bound to lead to economic confusion and the misallocation of resources he maintained.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; MISES; Ludwig von; history of economic thought; regulation; socialist economy

Human Freedom and the 'Reality of Society': Origins and Development of Karl Polanyi's Ideas during the Interwar Period - Thomasberger, Claus (History of Economic Thought, 2005)
Karl Polanyi's most famous book, The Great Transformation, contains several ideas and theoretical notions which are at the heart of long-lasting controversies throughout the social sciences. Categories such as "double movement," "embeddedness," "disembedding," "market society," or "social freedom" have proved to be fruitful notions not only in anthropology, but also in sociology, political sciences, and economic history. The recent three volume publication of Karl Polanyi's writings during the interwar period–including published articles and unpublished manuscripts–opens for the first time the possibility to have a closer look at the origins and the development of some of Polanyi's concepts during the interwar period. In the paper titled "Human Freedom and the Reality of Society–Origins and Development of Karl Polanyi's Ideas during the Interwar Period," Claus Thomasberger addresses Polanyi's idea of a polar relationship between human freedom and the "reality of society." The paper offers new insights, discussing central questions which are crucial to the understanding of Polanyi's reasoning: Where are the roots of his central categories? What influence did Marx have on Polanyi's thinking? What is the relationship between Polanyi's approach and the Austrian School of Economics? Is it appropriate to read his work in terms of an institutional approach? In order to give an answer to these questions, the paper goes back not only to the 1930s, but to the 1920s as well. As it demonstrates, Polanyi had already developed the core ideas of his thinking in Vienna, participating actively in the discussions between the Austrian School of Economics and Austro-Marxism about the possibilities of a socialist society.
Economics; Philosophy
Keywords: history of economic thought: individuals; reality of society

Polanyi, Chayanov, and Lessons for the Study of the Informal Sector - Özveren, Eyüp (Journal of Economic Issues (Association for Evolutionary Economics), 2005)
This article offers an alternative institutional economic approach to the informal sector by interpreting the works of economists Karl Polanyi and Alexander Vasil'evich Chayanov. Far from withering away, the informal sector continues to occupy an important place within economies in general and within the so-called developing economies in particular. Relatively speaking, the informal sector is inferior and more spontaneous, if not actually incomplete. Within the informal sector there are numerous small competitive firms, free entry, market-determined factor and product prices, together with a concentration of petty retail and services, labor-intensive production processes, and low productivity. According to Polanyi, one major drawback of mainstream economics is the insistence that the market mode is synonymous with the economy, and, under the weight of this assumption, formalistic economic analysis is assumed to be universally applicable to the study of all times and places. As a consequence, mainstream economists see markets where there are none.
Economics
Keywords: CHAYANOV; Alexander V.; POLANYI; Karl; 1886-1964; economic sectors; economics; informal sector (economics); labor productivity; labour productivity; small business

Beyond Boganism - Brown, Beth; Brown, Doug (Journal of Popular Culture, 2005)
The article analyzes the global economy by subjecting it to an interpretive scheme derived from popular culture Boganism, an Australian colloquialism or street slang used by teenagers. Boganism, the social phenomenon of being both unaware and irresponsible, is the result of a particular type of human abandonment. This abandonment is linked to the new hypercapitalism of globalization. The article will establish the structural roots of boganism, examine the case of the abandonment of U.S. youth, and conclude with reform recommendations necessary to shift us beyond boganism to a culture of sustainability. Karl Polanyi, a Hungarian economist, argued a half century ago that the birth of capitalism meant the emergence of what he called the disembedded economy. Polanyi's essential problem with capitalism, when it emerged in the sixteenth century, was that it creates a society in which everyone is dependent on markets to meet their basic needs. The pace of life has clearly increased with the maturation of capitalism and industrialism. But with the high-technology revolution, accompanied as it has been by the globalization of capitalism, what is happening is acceleration of everyday life, the economy, market transactions, and much more. Stratification: relationships of supra- and subordination, relations of domination and injustice. These are the social dimensions and institutional, structural relations between people and groups that have played defining roles in social, political, and economic analysis over the last three centuries of industrialism. Categories of stratification include classism, racism, statism, and sexism, and others. Along with these, we can add boganism.
Political Science; Economics
Keywords: capitalism; disembedded economy; disembeddedness; globalization; popular culture; socioeconomics

The fruits of intellectual production: economic and scientific specialisation among OECD countries - Laursen, Keld; Salter, Ammon (Cambridge Journal of Economics, 2005)
This paper brings together data from 17 OECD countries on scientific publications, patents and production, to explore the relationship between scientific and economic specialisation for 17 manufacturing industries. Since Marx, there has been a fundamental debate in economics about the link between science and the economic system. Marx argued that the needs of production shape scientific developments and that science has become a factor of production, whereas Polanyi argued that developments in science are largely independent of the economic sphere. Using a panel data model and econometric estimations at the industry level, the paper derives some hypotheses from the two positions and finds that, while the overall evidence on the link between national production and scientific specialisation is mixed, it is important to have high levels of relevant to-the-industry scientific strength per capita in order to be specialised in science-based industries.
Economics
Keywords: bibliometric data; econometrics; industries; international economic specialisation; manufactures; manufacturing industries; patent laws & legislation; patent suits; science & industry; scientific specialisation

Karl Polanyi et la séparation institutionnelle entre politique et économie - Buğra, Ayşe (Raisons politiques, 2005)
This article explores Karl Polanyi’s analysis of the institutional separation of politic and the economy in the context of the 19th century market economy. The contribution his analysis could make to the quest for viable alternatives to the contemporary neo-liberal international order depends on how we construe two key concepts in his work, “disembeddedness” and “countermovement”. In this regard the author suggests that: 1) In Polanyi’s work the disembedded economy appears not as a sociological reality but as a political project, and 2) Polanyi’s analysis of the countermovement does not justify all types of resistance to the market economy as humane and politically acceptable.
Economics; History
Keywords: institutional separation

Two heterodox economists: Neurath and Karl Polanyi - Giandomenica, Becchio (MyScienceWork Working paper No. 11/2005 Università di Torino 1, 2005)
This paper is based on the idea that between the 1920s and the mid-1930s in Vienna there were two forms of heterodox economic theory: the Austrian economic school headed by Ludwig von Mises and another interesting form of heterodox economics opposed to the Austrian school (above all politically) and pursued by various social thinkers (Otto Neurath, Karl Polanyi, Otto Bauer, Felix Schaffer, Felix Weil, Jacob Marschak). They were engaged in the debate on the possibilities of a planned economy: Austrian socialist economists proposed a sort of ‘third’ way between pure capitalism (whose Viennese stronghold was the Austrian economic school) and orthodox communism à la Kautzsky (deeply rooted in Germany). This paper focuses on the affinities between Neurath and Polanyi’s economic thought: despite some major differences between them, they shared a common philosophical background on which they founded their heterodox economic theory. After a brief historical premise, there is a first part, which deals with the debate on a planned economy and a second part, which deals with the influence of Neurath on the Polanyi’s vision of the faults of the neoclassical economic theory: the concepts of “disembedded economy” and of the so-called “economicistic fallacy”. NEURATH AND POLANYI IN VIENNA Neurath described himself as a ‘social engin
Economics; Philosophy
Keywords: Austrian economic school; NEURATH; Otto; economics; heterodox economics; philosophy; political science

Le port de commerce : un concept en débat - Graslin, Laetitia; Maucourant, Jérôme (Topoi, 2005)
Economics; History
Keywords: Dahomey and the Slave Trade; port of commerce

Le troc et la monnaie dans la pensée de Polanyi - Maucourant, Jérôme (2005)
Relire K. Polanyi nous affranchit d'une double illusion. Selon la première, l'homme est essentiellement un atome utilitaire exploitant les gains supposés de l'échange, cette vieille « fable du troc » n'étant pas remise en cause par l'économie des « coûts de transaction ». La seconde illusion, construction hétérodoxe voulant s'affranchir de cette fable, attribue à la monnaie les traits d'une institution aussi transhistorique qu'universelle. Certes, de nombreux phénomènes qualifiés de « troc » sont en réalité issus de la destruction d'ordres monétaires. D'ailleurs, K. Polanyi, commentant Aristote, montrait déjà que le dogme de la naturalité du troc est une projection des a priori de la société de marché. Mais, ceci ne signifie pas que la monnaie soit « souveraine » : seules les communautés politiques sont souveraines, seule la réciprocité, au sens de l'école maussienne, est un universel, le troc pouvant être « enchâssé » dans l'économie. Review Polanyi frees us a double illusion. According to the first, man is essentially a utilitarian atom exploiting the supposed gains of exchange, this old "barter fable" not being called into question by the economy of "transaction costs". The second illusion, a heterodox construction wishing to free itself from this fable, attributes to money the features of an institution as transhistorical as a universal one. Certainly, many phenomena called "barter" are in fact derived from the destruction of monetary orders. Besides, K. Polanyi, commenting Aristotle, already showed that the dogma of the naturalness of barter is a projection of a priori of the market society. But this does not mean that money is "sovereign": only political communities are sovereign, only reciprocity, in the sense of the Maussian school, is a universal, barter can be "enshrined" in the economy.
Economics; Political Science
Keywords: barter; universal barter

L'ère de l'opulence selon Polanyi - Maucourant, Jérome; Vivel, Christel (Economies et sociétés, 2005)
L'article expose la problématique d'un texte peu connu de Polanyi datant de 1959. Prétextant un commentaire de L'ère de l'opulence de Galbraith, il soutient que le naturalisme de l'économie dominante nous interdit de comprendre la signification véritable de la rareté. Polanyi montre alors que les oppositions classiques entre liberté et égalité, économie et démocratie, peuvent être dépassées dans le cadre d'une société nouvelle abolissant la séparation institutionnelle de l'économique et du politique. Ces thèses de Polanyi sont imprégnées d'un aristotélisme tenant compte des déchirures sociales que furent le machinisme et les fascismes. KM: One aims at presenting a unknown Polanyi's text. Starting with a comment of the Affluent Society from Galbraith, we explain that the mainstream economics'naturalism prevents us from understanding the actual significance of scarcity. Polanyi shows that the classical oppositions between liberty and equality, economy and democracy can be overcame in the frame of a brand new society in which the institutional line between economics and politics should be abolished. This is sustained by an aristotelism that takes into account the social breaks produced by machinism and fascisms.
Economics; Sociology
Keywords: opulence; rareté

The Transition between the Old and New Traditional Economies in India - Rosser, J. Barkley; Rosser, Marina V. (Comparative Economic Studies (Palgrave), 2005)
We extend Karl Polanyi's traditional economy concept to modern economies with advanced technology that are embedded in a traditional socio-cultural framework. This is the New Traditional economy, seen in parts of the Islamic world and with the Hindu nationalist movement in India. However, rural India is also the largest repository of the Old Traditional economy with its Hindu caste and jajmani system of reciprocal labour relations. The changes in India's complexly mixed economy, with its increasing market and strong planned elements, constitute a transition from the Old to the New Traditional economy. We shall consider this transition both ideologically and systemically.
Economics
Keywords: Hinduism; India; caste; economics; labor; labour; markets; nationalism; new traditional economy; old traditional economy; transition

Endogenous Preferences and Embeddedness: A Reappraisal of Karl Polanyi - Rodrigues, João (Journal of Economic Issues (Association for Evolutionary Economics), 2004)
This article examines the relevance of the Karl Polanyi's contributions to economics in general and to the issue of endogeneity of human preferences in particular. Although Polanyi never spoke of endogenous preferences, one can capture in his work a vision of the historical specificity and institutional dependence of human purposes and reasons for behavior. It is undeniable that in Polanyi there is a certain tendency to overlook human volition and to fall into a kind of institutional determinism. Nevertheless Polanyi recognizes the scope for deliberate human action when he defines institutions as the embodiments of human meaning and purposes. Furthermore, in Polanyi's work, there is a very clear awareness of the complexity of the motives for human action and a defense, which is continuously reaffirmed, of the plurality of reasons to act in economic interactions and their relation to the patterns of interaction that are dominant. Nevertheless, there is a lack of a clear and well-systematized account of the possible causal links by which institutions influence human preferences. His substantive economy takes morality into account, in the sense that its foundations lie on the recognition that man is a moral being with duties toward himself and others, with an understanding of what is good and what is bad and that these moral codes exert a powerful influence upon economic affairs.
Economics
Keywords: economic anthropology; embeddedness; endogenous preferences; ethics; human behavior; institutional economics; social sciences

Pinochet meets Polanyi? The Curious Case of the Chilean Embrace of "Free" Market Economics - Cypher, Jame M. (Journal of Economic Issues, 2004)
This article argues, within the context of Karl Polanyi's work, that the common view of Chile is doubly miscontrued, in terms of free market economics. Events since the end of the dictatorship (1989) tend to confirm Polanyi's hypothesis in 'The Great Transformation' (1957; discussed in the following section) while at the same time negating the Chicago School's view that a free market society could be built–even under a dictatorship. In Chile from September 1973 onward through 1989, the Chicago School–inspired economists known as the Chicago Boys, engaged in what would appear to be the most determined utopian endeavor of economic liberalism to set up a self-regulating market system. It is the hypothesis of this paper that the Chicago School failed spectacularly in this effort and that the credit they have widely received for successfully remaking the Chilean economy properly belongs to the antithesis of the Chicago School–successful state-led efforts to restructure the economy and foster development. Far from the fictitious utopia of the free market, under the dictatorship the state was also heavily involved in projects designed to massively transfer economic rents to the private sector. Consistent with Polanyi's thesis, the Chicago School was able to drastically reduce Chile's social legislation, labor legislation, and social controls over the exploitation of the natural resources of Chile only within the context of a military dictatorship. While Chile's elected governments have embraced the Chicago School's faith in unlimited and unregulated free international trade, in the area of social legislation and labor legislation there are very strong indications that civil society is systematically and effectively striving to overcome the retrograde steps imposed by the dictatorship.
Economics
Keywords: Chicago school of economics; Chile; economic conditions; economics; free enterprise; politics and government

Heilbroner and Polanyi: A Shared Vision - Dimand, Robert W. (Social Research, 2004)
The article presents the shared vision of Polanyi and Heilbroner. This paper focuses on the parallel ideas of economists Karl Polanyi and Robert Heilbroner. Their concept on the role of market system in the emergence of economics as a field of study is explained. More issues included are the requirements for the transformation of a pre-market society into a true market, Polanyi's influence to several economists, and relevance of the Polanyi/Heilbroner vision of the market system to the postcommunist countries transition to the market.
Economics
Keywords: HEILBRONER; Robert; economics; economics - statistical methods; economists; markets; social sciences; societies; statistics

Re-Inventing Karl Polanyi: On the Contradictory Interpretations of Social Protectionism - Drahokoupil, Jan (Sociologický Časopis / Czech Sociological Review, 2004)
The ideas of Karl Polanyi's The Great Transformation have often been referred to in the recent debates that have emerged as a reaction to the rise of neoliberal policies. This paper deals with contradictory interpretations of the notion of social protectionism in the work of Karl Polanyi. There are two opposing interpretations distinguished here. The first interprets social protectionism as a balancing principle of economic liberalism. The second understands social protectionism as a part of market pathology. In order to assess the validity of competing interpretations, the author puts forth an account of social protectionism in the context of Polanyi's theory of the economy and society. The author concludes that the popular notion of social protectionism as a balancing principle of economic liberalism does not correspond to Polanyi's theory. In addition, the author offers a skeptical commentary on the utility of Polanyi for understanding social protectionism in social analysis.
Sociology; Economics
Keywords: critique; social protectionism

Polanyi and the History of Capitalism: Rejoinder to Blyth - Hejeebu, Santhi; McCloskey, Deirdre (Critical Review, 2004)
Mark Blyth's rebuttal to our constructive critique of Polanyi "blithely" takes for granted the accuracy of Polanyi's now-outdated historiography of capitalism–by means of a loose, overly expansive definition of capitalism that question-beggingly equates it with modernity. Blyth emphasizes the need to view markets as "socially embedded," with which we agree–but he appears not to take account of the individual self-interest that is thus embedded. Similarly, he asserts a priori the role of ideas in history, in parallel to the economists he condemns (unfairly) for reading ideas out of history a priori. All of this poorly serves the cause of extracting Polanyi's welcome emphasis on social embeddedness and on the empirical from the ideological and methodological certitudes and errors in which The Great Transformation placed them.
Economics
Keywords: BLYTH; Mark; history of economic thought: individuals

Social Capital, Karl Polanyi, and American Social and Institutional Economics - Carroll, Michael C.; Stanfield, James Ronald (Journal of Economic Issues, 2003)
Economics
Keywords: World Bank; communities; division of labor; evolutionary economics; institutional economics; market economies; market economy; social capital; social networks; socioeconomics; solidarity

The Life and Work of Karl Polanyi/Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation - Dimand, Robert (Review of Radical Political Economics, 2003)
This article reviews two books about the thoughts of economist Karl Polanyi including "The Life and Work of Karl Polanyi," edited by Kari Polanyi-Levitt, and "Karl Polanyi in Vienna: The Contemporary Significance of the Great Transformation," edited by Kenneth McRobbie and Polanyi-Levitt.
Economics
Keywords: Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation (Book); Life and Work of Karl Polanyi; The (Book); MCROBBIE; Kenneth; POLANYI LEVITT; Kari; book review; economics; nonfiction

Avec Mauss et Polanyi, vers une théorie de l'économie plurielle - Laville, Jean-Louis (Revue du MAUSS, 2003)
Mauss and Polanyi sketched the theoretical foundations of a pluralist approach to the economy and began a reflection on social change that was not satisfied with the ritual evocation of a reversal of the system. In other words, instead of an abstract call to an alternative economy, the concrete path of "altereconomies" opens the field of possibilities.
Sociology; Economics
Keywords: altereconomies

Theorizing the 'Third Sphere': A Critique of the Persistence of the 'Economistic Fallacy.' - Adaman, Fikret; Madra, Yahya M. (Journal of Economic Issues, 2002)
The paper seeks to investigate, from a methodological and ontological perspective, different ways of theorizing the third sphere–the set of activities that can be captured by neither the price mechanism of the markets nor by governmental transactions. The first aim is to elucidate the constitutive elements of the third sphere by deploying Polanyi's forms of integration (reciprocity, redistribution, and exchange). The second is to survey the ontologically individualist and methodologically formalist literature on the third sphere. After elucidating the coexisting sets of behavioral essences in contemporary ontologically individualist and methodologically formalist models of third-sphere activities, the paper claims that this proliferation of behavioral essences can only lead to a methodological impasse. The paper concludes that only with a committed recognition of the heterogeneity of the economy and the endogeneity of the economic subject will it become possible to better grasp the richness of third sphere activities.
Economics
Keywords: current heterodox approaches: institutional; economic methodology; economistic fallacy

The Contested Sovereignty of the Firm - Dietrich, Michael (Review of Political Economy, 2002)
This paper suggests that the firm can be analysed as a regulated system of contested sovereignty. The economic literature on the firm is categorised in terms of four different perspectives on sovereignty identified using the twin factors of power and authority. But rather than any single perspective being identified as analytically superior, it is argued that a system of contested sovereignty should be based on all four perspectives. Following this, a Polanyi-inspired analysis of firm regulation is presented in which the regulation of the firm emerges to control the costs of free markets. However, this regulation depicts firm sovereignty as complex and contested rather than simply an optimal response to market failures.
Economics
Keywords: business enterprises; economics and literature; firm regulation; firm sovereignty; political economy

Transnational Pharmaceutical Corporations and Neo-Liberal Business Ethics in India - D'Mello, Bernard (Journal of Business Ethics, 2002)
The author critiques the expedient application of market valuation principles by the transnational corporations and other large firms in the Indian pharmaceutical industry on a number of issues like patents, pricing, irrational drugs, clinical trials, etc. He contends that ethics in business is chiseled and etched within the confines of particular social structures of accumulation. An ascendant neo-liberal social structure of accumulation has basically shaped these firms' sharp opposition to the Indian Patents Act, 1970, government administered pricing, etc. The author contends that the practice of neo-liberal economics is strongly associated with a "one dimensional" ethics that privileges market valuation principles over all others. This seems to inevitably generate a social counter-movement that struggles for social protections. He critiques neo-liberal business practices from a perspective that derives from the work of the economic anthropologist Karl Polanyi. Before the present phase of liberalization in India, markets were "managed", but without a "welfare state" in place. Moving toward deregulation of the markets without a welfare state in place is unethical. Keeping the debilities of the institutional framework of public policy in mind, the author adopts a Polanyian perspective that places its trust and hope in the growing social legitimacy of the counter-movement in opposition to both neo-liberal business practices and the degenerate behavior of state agencies.
Political Science; Economics
Keywords: India; business ethics; intellectual property; international business enterprises; pharmaceutical industry; socialism

Le bénévolat dans une approche substantive de l'économie, Abstract - Gardin, Laurent (Revue française des affaires sociales, 2002)
RésuméDifférents travaux ont délivré des méthodologies et des données quantifiant l’apport du bénévolat en temps et en argent. Ces préoccupations amènent, dans le sillage des travaux de Karl Polanyi, à appréhender l’économie de manière substantive comme la dépendance de l’homme par rapport à la nature et à ses semblables. Une telle analyse montre qu’il n’y a pas nécessairement une concurrence entre ces différents registres économiques mais qu’une hybridation des ressources peut se mettre en place au service des projets associatifs. Si le bénévolat permet aux pouvoirs publics de faire des économies pour le développement de ces services, il permet aussi de développer des services plus en adéquation avec les demandes sociales, et conduit à une évolution des politiques publiques et à un déploiement de leurs actions pouvant conduire, paradoxalement, à une croissance des dépenses publiques. À partir d’exemples étudiés dans le champ de l’aide aux personnes âgées et handicapées, cette contribution vise à donner les éléments permettant la valorisation du bénévolat, à dresser une typologie des fonctions remplies par le bénévolat et à mesurer son influence sur les différents registres économiques et notamment la redistribution., Various studies have provided methodologies and data for quantifying the contribution of voluntary service in both time and money terms. This work causes one, in the wake of the work by Karl Polanyi, to apprehend the economy in substantive terms – along with the dependence of man compared to nature and his fellow creatures. Such an analysis shows that there is not necessarily a competition between these various economical registers, but that a “hybridization” of resources can be set up in the service of associative projects. If voluntary service makes it possible for the public authorities to make savings when developing such services, it also makes it possible to develop services more in line with social needs, which leads to changes in public policies and to a deployment of their actions, which can lead, paradoxically, to increased public expenditure. This article thus aims to understand the influence of voluntary service on the various economical registers, and in particular on redistribution from examples studied in the field of the assistance to the old and handicapped people, this contribution aims giving the elements allowing the valorization of the voluntary help, drawing up a typology of functions filled by the voluntary help and at measuring its influence on the various economic registers and in particular the redistribution.
Sociology; Economics
Keywords: substantiveness; voluntary service

The Construction of Market Institutions in Russia: A View from the Institutionalism of Polanyi - Sánchez-Andrés, Antonio; March-Poquet, José M. (Journal of Economic Issues, 2002)
This article presents information on the construction of market institutions in Russia and includes the institutional conception provided by analyst Karl Polanyi. Polanyi's main ideas will be expounded in regard to his interest in analyzing the transition. These ideas will be adapted to the object of study and then specified so that they will be efficient criteria for analyzing the present economic transition. Second, the results obtained will be applied to the Russian case, and an attempt will be made to draw some conclusions about whether Russia is moving toward a market economy. Although several distinct parts of the work of Polanyi may be of great interest in analyzing the transition process that is occurring in countries that until the 1990s were organized by central planning.. This paper discusses only the aspects which are most closely related to the construction of market economies will be mentioned. According to Polanyi, the commercialization of productive factors and money are among the determining elements for the construction of an economic market.
Economics
Keywords: Russia (federation); analysts; central planning; economic reform; industrialization; markets; transition economies

Reply to Professor Levine on Rhetoric and Reality in American Welfare History - Kern, William S. (Journal of Economic Issues (Association for Evolutionary Economics), 2001)
The article replies to professor David Levine's rhetoric and reality in American welfare history. The author largely agrees with Professor Levine's conclusion that the impact of the application of the principles of 1834 on contemporary welfare reform is "far more potent rhetorically than it is in fact" (733) and that "the slowly expanding mild welfare state is here to stay" (741). Levine argues that this is the result of the emergence and persistence of a "New Deal consensus" regarding the responsibility of government to secure macroeconomic stability and individual security that survives from its origin in the 1930s till today. The questions that arise are why this consensus emerged when it did and why it persists. In his paper the author attempts to explain why the reemergence of the rhetoric and practice of welfare reform had occurred, and he argues that an answer could be found in ideas developed by Karl Polanyi in The Great Transformation (1944). It had been argued that the logic of the self-regulating market required the denial of a right to life outside the market. This was affirmed in the passage of the New Poor Law and in the rhetoric and practices of current welfare reform. However, Polanyi's Great Transformation also provided us with an explanation of the factors which underlie the emergence of the New Deal consensus in the 1930s, the persistence of the welfare state, and the largely rhetorical impact of the principles of 1834 on current welfare reforms.
Economics
Keywords: United States; economic conditions - United States; economic history; macroeconomics; public welfare; reforms; welfare economics

Une lecture de Karl Polanyi - Maucourant, Jérôme (L'Économie politique, 2001)
Vouloir débattre de questions d’économie politique, comme la présente revue et toute l’oeuvre de Karl Polanyi (1) nous y invitent, semble relever, à l’aube du XXIe siècle, d’une absolue gageure. Sur le plan académique, l’économie politique s’est métamorphosée en une « science » économique fondée sous le double sceau de l’individualisme méthodologique et de l’affirmation d’une dichotomie totale entre faits et valeurs. A l’inverse, l’anthropologie de Polanyi se fonde sur un socialisme humaniste qui fut nourri par des lectures de Karl Marx et un ancien projet de « sociologie chrétienne ». Sur le plan théorique et politique, Karl Polanyi cherche à justifier une conception de la démocratie comme contrôle social de notre devenir. Dès 1922, chose qui est peu soulignée, il tente de penser un modèle de socialisme décentralisé pour répondre à ce qu’il considère comme l’impasse du libéralisme et l’erreur que constitue la planification centralisée.
Economics; Political Science

Interpreting the Consequences of Midwestern Agricultural Industrialization - King, Martin Burce (Journal of Economic Issues (Association for Evolutionary Economics), 2000)
The article focuses on the interpretation of consequences of Midwestern agricultural industrialization. The nature and consequences of the industrialization of agriculture are well documented in academic research and in the popular press. Interpretations of the process vary in reflection of the diverse perceptions of the nature and overall significance of industrialization. Suggested policies range from a "hands-off" to a "prohibit and prevent wherever possible" approach. Both approaches are unrealistic because they fail to recognize the historical context in which agricultural industrialization is taking place. In this paper, the author presents a historical context for the process, using nineteenth-century Illinois and the industrialization of swine production as examples of commercialization and industrialization of Midwestern agriculture, respectively. The author integrates the work of Karl Polanyi and K. William Kapp into the discussion to provide a foundation for realistic policy and to demonstrate the relevance of an institutionalist perspective to the formation of contemporary agricultural policy.
Economics
Keywords: KAPP; Karl William; agriculture; commercialization; crop insurance; economic theory; evolutionary economics; industrialization; production (economic theory); rural industries

The Reproving of Karl Polanyi - Hejeebu, Santhi; McCloskey, Deirdre (Critical Review, 2000)
Karl Polanyi's The Great Transformation has had enormous influence since its publication in 1944. In form, this influence has been salutary: Polanyi targets one of the main weaknesses of modern economics. But in substance, Polanyi's influence has been baneful. Mirroring the methodological blindness he criticizes, Polanyi insists on the all-or-nothing existence/nonexistence of laissez faire–and on its all-or-nothing goodness/badness.
Economics
Keywords: critique; history of economic thought: individuals

Freedom and the Market (An Analysis of the Anti-globalization Movement from the Perspective of the Theoretical Foundation of the Evaluation of the Dynamics of Capitalism by Polanyi, Hayek and Keynes.) - Nikitin, Pavel V.; Elliott, John E. (Forum for Social Economics, 2000)
Those who believe that the free market is positively related to both economic efficiency and individual freedom are prone to regard resistance to the establishment of the global market essentially free from any serious sociopolitical constraint as a politically insignificant expression of impatience, ignorance, and hypocrisy. This article attempts to endow the manifestation of discontent with the status quo evident in public protests in Seattle and Washington DC with political significance through explicating it as an expression of a fundamental conflict between economic efficiency and individual freedom inherent in the global implementation of the principle of self-regulating markets. This analysis of the anti-globalization movement is conducted from the perspective of the theoretical foundation of the evaluation of the dynamics of capitalism by Polanyi, Hayek, and Keynes, and its conclusions are brought to bear upon the validity of their contesting views of the relationship between economic efficiency and individual freedom.
Economics
Keywords: anti-globalization movement; capitalist systems; international economic order; political economy

Karl Polanyi's Forms of Integration as Ways of Mapping - Schaniel, William C.; Neale, Walter C. (Journal of Economic Issues, 2000)
Researcher Karl Polanyi's "forms of integration"–redistribution, reciprocity, and exchange–have been much used to describe and explain various economies. Such mapping presents information about the sources and destinations of the flows of material means in each society in ways that are easily correlated with the variables that most thoroughly and simply account for the flows of material means in different societies. Mapping may be looked upon as the selection of a "projection" for portraying the flows of material means. The diagrams below illustrate the discussions of each form of integration and are examples of mapping. As is the case for projections selected for geographical mapping, for each way of mapping a form of integration the criterion of the appropriateness of the choice of projection is analogous to a mathematical function. The independent variables would be information about the social system; the dependent variable would be the directions in which the material means flow. The merits of the choice of projection are simplicity and the accuracy with which the directions of flow are portrayed.
Economics
Keywords: commercial policy; economics; forms of integration; functions; mappings (mathematics); mathematics; social sciences

Working Paper No. 63, On Karl Polanyi and His Conception of Fascism - Mistkawi, Serene (Working Papers in Economics, 2022)
This inquiry seeks to establish that the writings of author Karl Polanyi offered insights into key variables and historical conditions that gave rise to the system we know of as “fascism.” Integral to his insights, Polanyi describes economic conditions attendant for fascism to emerge, with one condition noted as widespread and persistent unemployment. Polanyi stresses that fascism needs to be understood as reactionary, a responding to features integral to classical liberalism. Considering a broad historical context Polanyi teaches us of the political conditions necessary for fascism to emerge and take form as political movements wielding power. He considers conflicts in aims between economic and political institutions. In addition, Polanyi analyzes some implications of a changing market, as well as some effects that a changing market might have over individual freedoms, as well as some of the complexities that can be associated with regulation.
Economics
Keywords: classical liberalism; currency; fascism; interventionism; regulation

Karl Polanyi’s ‘socialist accounting’ and ‘overview’ in the age of data analytics - Rief, Silvia (New Political Economy, 2022)
Digital capitalism’s information infrastructure is the subject of contentious debates concerning its transformative effects on the political economy and society. A frequent proposition, referring to older arguments of the ‘socialist calculation debate’, is that with big data analytics the pro-market arguments of neoliberal economists such as Hayek or Mises become obsolete. This article critically examines this proposition by drawing on Karl Polanyi’s notion of overview; a core theme in his outlines of a socialist economy and accounting written in the 1920s. In these contributions to the early Austrian socialist calculation debate, Polanyi discusses how to gain knowledge of the economic and social processes in such a way that the economy can be democratically governed according to its socialist aims and purposes. This article highlights the relevance of Polanyi’s work on socialist accounting, along with his later perspectives on technology and on social scientific method, for reflecting upon data- and algorithm-driven economic governance. Polanyi’s critical analysis of abstraction effected through methods of knowing suggests a sceptical stance vis-à-vis current versions of technological ‘solutionism’, which places its faith in data and algorithms as tools for economic and social, or socialist, planning.
Sociology; Economics
Keywords: Karl Polanyi; accounting; data analytics; digital socialism; economic theory; overview; socialist accounting; socialist calculation

Devlet, Piyasa ve Toplum: Karl Polanyi ve Friedrich A. Hayek Üzerine Bir İnceleme - Güder, Mustafa; Atalay, Kürşad (İzmir İktisat Dergisi, 2022)
Individual life in general; It is determined by political, economic and sociological structures. The main forces that shape these structures are the state, market and society, respectively. When the views of Karl Polanyi and Friedrich Hayek on the state, market and society are considered comparatively, a holistic approach can be reached for understanding human life. In this context, the two thinkers have been the pioneers of two opponents lines in social sciences by putting forward opposite perspectives on the same phenomena. In the study, it is determined that these thinkers have a descriptive power in the ideological classification of later studies. Based on this, the views of the thinkers; It is put forward that it represents an "ideological pH value" for the social sciences. Polanyi draws attention that the ideals of individual freedom and equality claimed by the market system are not realized; brings social values to the fore.. Hayek claims that the market is the best institutional order that ensures human well-being and freedom. This study aims to discuss Hayek's free market view and Polanyi's embedded economic system with its political, economic and social aspects comparatively.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; devlet; market; piyasa; society; state; toplum

The political trilemma of contemporary social-ecological transformation – lessons from Karl Polanyi’s The Great Transformation - Novy, Andreas (Globalizations, 2022)
This article advances Rodrik's political trilemma of the world economy by using insights from Polanyi’s The Great Transformation, which helps to grasp the interwoven dynamics of long-term transformations due to climate change and geopolitical reordering on one hand, and on the other short-term political ruptures due to countermovements. Rodrik's globalization trilemma shows the incompatibility of hyperglobalization with the need for an enlarged democratic policy space. Its nodes (globalization, nation state and democracy), however, have to be redefined to grasp contemporary dynamics of deglobalization. Based on a modified political trilemma of contemporary social-ecological transformation, I discuss and compare three visions and the resultant strategies: (1) Liberal globalism, focusing on hyperglobalization and individualism, (2) nationalistic capitalism, stressing national sovereignty and authoritarian governance, and (3) foundational economy based on planetary coexistence which combines selective economic deglobalization with a strengthening of a place-based foundational economy, and their respective social-ecological infrastructural configurations.
Political Science; Economics
Keywords: Great Transformation; The (Book); Polanyi; deglobalization; foundational economy; hyperglobalization; social-ecological transformation

Discussions around Argentine Capitalism: Economic Debate and Contribution of Karl Polanyi for Our Days - Rossi, Ignacio Andrés (2022)
The article proposes to address the current discussions about national capitalism and the Argentine economy from a set of canonical ideas of the work of Karl Polanyi. Argentina, which for several decades has been going through recurring crises in its economic model, awakens a plurality of voices from social scientists and specialized journalists who debate the problems, limitations and projections of national capitalism. For this, we have surveyed these discussions, to a greater extent, from the specialized press and the recently published bibliography, paying attention to the theoretical, interpretative and ideological proposals that allow us to generate relationships with Polanyi's theory. It was concluded that the latter's ideas about the functioning of capitalism, markets, the State and contemporary social dynamics provide significant conceptual background to frame the current discussions among social scientists about the Argentine economy.
Economics
Keywords: Argentina; capitalism; development; stability; state

Karl Polanyi and the Reappraisal of Happiness Economics - Özveren, Eyüp; Gürpinar, Erkan; Karagöz, Ufuk (Journal of Economic Issues, 2021)
Happiness economics unearths the undesirable effects of economic growth and criticizes the economic model based on the belief in the supremacy of market relations over the relational bonds of society. Economic growth brings about substantial increases in material well-being; yet, it has the potential to destroy the social and environmental fabric of society. This is visible in the post-World War II cross-country variability of the subjective well-being measures, which shows the importance of relational goods and associational activities. These themes echo Karl Polanyi’s concerns over the destructive effects of the self-regulating market mechanism. In this paper, we demonstrate the relevance of the interdisciplinary work of Polanyi for happiness economics. We argue that Polanyi’s conception of the self-regulating market system comes together with the spread of unhappiness. The treatment of labor as a fictitious commodity is of utmost significance in this respect. No less important is the similar degrading of land, a proxy for environment. Furthermore, the distinction Polanyi maintained between “exploitation” and “cultural degeneration” in assessing the Industrial Revolution is useful for this critique. In essence, Polanyi’s approach is relevant to explain the deterioration of social relations, which is thought to be the ultimate reason behind the happiness paradox.
Economics
Keywords: Karl Polanyi; consumption; happiness; hedonism; self-regulating market system

New Limits of the Neoliberalism: Society and Market - Vidal, Laura; Correa, Eugenia (Journal of Economic Issues, 2021)
Neoliberalism has been able to change the markets and the economy of societies around the world. These transformations are especially important with regards to fictitious commodities: land, labor, and money. However, the 2020 pandemic imposes new limits, when life itself is at risk globally. This work highlights the major neoliberal reforms relating to fictitious commodities, the difficulties of society to resist and create counterweights. The health crisis that has emerged with the COVID-19 pandemic is the result of decades of over-exploitation of nature and human beings. The reforms over fictitious commodities, especially labor, have led to a constant and systematic decline of society. This article is supported by the theoretical legacy of Karl Polanyi and Kari Polanyi Levitt that allows us to consider the most important trends of neoliberal reforms and their main objectives.
Economics
Keywords: fictitious commodities; health crisis; neoliberal counterrevolution; neoliberalism

Wirtschaftsethik der ›always embedded market economy‹. Überlegungen zu einer Idee von Polanyi - Haase, Michaela (Zeitschrift für Wirtschafts- und Unternehmensethik, 2021)
Capitalism is a social relation that cannot be reduced to the characteristics associated with it - markets, private property, profit and profit orientation. This relation can be shaped in different ways. The article refers to Karl Polanyi’s idea of the ›always embedded market economy‹ in order to develop basic characteristics of an example of post-capitalist economic ethics. Alternate abstract: Der Kapitalismus ist ein soziales Verhältnis, das sich nicht auf die mit ihm in Verbindung gebrachten Merkmale - Märkte, Privateigentum, Gewinn- und Profitorientierung - reduzieren lässt. Dieses Verhältnis kann auf verschiedene Weise ausgestaltet werden. Der Beitrag referiert auf die Idee der ›always embedded market economy‹ von Karl Polanyi, um Grundzüge einer postkapitalistischen Wirtschaftsethik zu entwickeln.
Economics; Philosophy
Keywords: business and economics; capitalism; ethics; market economies; philosophy; private property

ТРАДИЦИОННАЯ РЫНОЧНАЯ ЭКОНОМИКА И ЕЁ АНТИЦИКЛИЧЕСКИЙ ПОТЕНЦИАЛ В ОЦЕНКАХ ИССЛЕДОВАТЕЛЕЙ XIX-XX ВЕКОВ - Анатольевич, Орлянский Евгений (Наука о человеке: гуманитарные исследования, 2021)
The article deals with the first stage of the market economic system - the traditional market economy. The traditional market economy is considered in the assessment of its main researchers. The main goal of the study is to identify the main characteristics and features of the traditional economy, which would explain the absence of pronounced cyclical elements in it. It is assumed that several essential elements of such an economy carry the strongest countercyclical potential. The article uses the methodology of comparative analysis, which will help to find common ground among the most famous researchers of the traditional market economy. The study of the traditional market economic system was carried out in the context of overcoming the stereotype of the closed development of economic processes and the impossibility of influencing them by non-economic factors. This is confirmed by the fact that most of the countercyclical elements of the traditional market economy are derived from the spiritual and ethical sphere. At the same time, an integral part of the article is the position that this economic system retains all the characteristic features of a market economy. The traditional market economy practically did not experience cyclical tendencies in its development. This was due to the fact that this economic system contained built-in elements that ensured the absence in the traditional economy of both cyclicality itself and periodic cyclical crises.
Economics

BRIE Working Paper 2020-6 What Polanyi Teaches Us: The Platform Economy and Structural Change - Eldred, Christopher (The Berkeley Roundtable on the International Economy, 2020)
The welfare system was meant to reduce the 9 vulnerability of citizens to the market, thereby containing the consequences of the market economy and labor commodification. [...] As an adaptation to the consequences of the market, the welfare system is an effort to cushion the effects of the market, not a change its underlying logic of commodification. [...] From this perspective, the political debates about the rules to be applied to the operations of the platform economy are part of the “second movement,” i.e., a reaction to the platform economy. [...] In contrast, to the industrial revolution where the capitalist moved production into the factory to develop greater control than was possible with the putting-out system, the platform extrudes the work and obligations outside the boundaries of the firm. [...] In actuality the relationship between the members of the ecosystem and the platform is hierarchical and based upon an extreme power asymmetry within which the ecosystem members are at the mercy of the platform which controls the nexus of relationships (Cutolo and Kenney, 2020).
Economics
Keywords: platform economy; welfare

Requisitos para el cambio transformativo: contribuciones de Karl Polanyi - Kirby, Peadar (International Review of Economic Policy-Revista Internacional de Política Económica, 2020)
Una pregunta clave que surge de la pandemia de coronavirus es qué se requiere para hacer de esta fase temporal un camino hacia el cambio transformador. O, como sucedió en gran medida después de la crisis financiera de 2008, ¿volverá la sociedad a una economía dominada por el crecimiento y cargada de carbono basada en una ética del individualismo radical y el consumismo desenfrenado, informada por recetas neoliberales? Este artículo se basa en el trabajo de Karl Polanyi (1886-1964) para ofrecer un marco teórico alternativo para guiar el cambio social transformador en la era del cambio climático. Comienza por identificar una característica clave del equilibrio entre la estructura y la agencia en la sociedad contemporánea, a saber, un optimismo tecnológico y propone un marco alternativo a través de la economía política. La segunda sección identifica los dos marcos teóricos clave que informaron las configuraciones dominantes de la economía política desde la Segunda Guerra Mundial: un marco socialdemócrata y un marco neoliberal. Se argumenta que ahora es necesario un nuevo marco. La tercera y más larga sección dibuja una gama de contribuciones conceptuales de Polanyi para ofrecer una teoría distintivamente diferente a la que ofrece el neoliberalismo. Estos incluyen: sociedad de mercado; diferentes significados de economía; mercancías ficticias; formas de integración; doble movimiento; descubrimiento de la sociedad; la persona humana y la libertad; y el poder de la tecnología. La sección final saca conclusiones.
Economics
Keywords: COVID-19; climate change; market society; neoliberalism

Karl Polanyi contre Ludwig von Mises - Pinault, Santiago (Austriaca. Cahiers universitaires dʼinformation sur lʼAutriche, 2020)
Les analyses de Felix Schafer, alors le plus proche collaborateur de Karl Polanyi (1886-1964), permettent de comprendre un débat entamé en 1922 à Vienne entre Polanyi et Ludwig von Mises (qui était alors le représentant le plus célèbre de l’école autrichienne). Les enjeux de leur opposition devaient structurer la pensée polanyienne en son entier. Dans les décennies suivantes, notamment les années 1940-1950 aux États-Unis, c’est en esquissant une approche de type sociologique que Polanyi allait paradoxalement élaborer, sur des catégories conjointes qu’il tire indissociablement de Max Weber et de Carl Menger, un paradigme que nous qualifions de « vieux (ou vétéro)-autrichien » en raison de son retour aux sources de cette tradition (prise au sens large). Le formalisme de Mises s’y intègre pour former une « branche formaliste » selon Polanyi, qui nous a peut-être laissé là sa plus féconde intuition.
Economics
Keywords: Austria; MISES; Ludwig von; WEBER; Max; 1864-1920; substantivisme

Economía de mercado, globalización y migración: retos y rostros de las personas vulneradas globales. Un análisis desde Karl Polanyi - Franco, Jefferson Frenel Junior Pierrelus (Contextualizaciones Latinoamericanas, 2020)
Este ensayo pretende demostrar cómo el mercado autorregulado que pregonael neoliberalismo es una falacia y que tiende tarde que temprano a acabar odestruir las propias condiciones sociales, ambientales y culturales que aseguranla vida en el planeta. Basado en una globalización financierista, en la privatización yen la liberalización de mercado, ese modelo se ha convertido en la mayor fábrica deempobrecidos, logrando cooptar y subordinar a los Estados a sus designios a travésde las grandes empresas transnacionales e instituciones económicas internacionales.La neo-esclavitud, la miseria, la precariedad y la violencia se han instalado como unmodo de ser y de vivir, aunadas a la emigración, debido a esa explotación, extracciónde recursos naturales a ultranza que lleva a cabo ese modelo económico imperante.Hay voces, manifestaciones, como la de Karl Polanyi, que quieren poner un freno a esemolino satánico, llamado neoliberalismo.
Economics; Political Science
Keywords: economía de mercado; globalización; globalization; market economy; migración; violence; violencia

Sustaining Democracy in an Era of Free Markets: Karl Polanyi’s Perspectives on the Politics of Finance - Scheiring, Gábor (Intersections. East European Journal of Society and Politics, 2016)
With the contemporary crisis of liberal democracy and the rise of illiberalism in the aftermath of the global financial crisis we need a theoretical framework that links modernization, crises and the fate of democracy. In my paper I attempt to show that Polanyi’s thinking represents such a framework. I focus on Polanyi’s historically informed political economic analysis of the tensions between liberal finance and liberal democracy. In the first section I reconstruct Polanyi’s political stance regarding democracy, socialism and the market. Based on this I will bring to the fore his often neglected views regarding the commodification of money and the tensions between international finance and democracy. Polanyi shows that monetary policy is not a technical but a deeply political question with major social implications. In the final section of my paper I conclude that Polanyi’s theory of the double movement and fictitious commodification can only be understood once we strip it of its excessive functionalism and bring it into dialogue with his political views. Polanyi urges to preserve the market by protecting the economy and society from the damages of excessive commodification: markets need to be protected from themselves.
Sociology; Economics
Keywords: Polanyi; democracy; double movement; fictitious commodities; finance

An Evaluation of Institutional Matrices Theory Which Was Designed to Illustrate Differences Between Russian and Western Political Economies - Hayden, F. Gregory (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
This article is devoted to the evaluation of the institutional matrices theory (IMT), which was designed to illustrate the differences between Russian and Western political economic systems. IMT has no matrix, and it is an ideological declaration rather than a theory. It is a set of assertions and assumptions that are adopted without evidence, and then hypostatized to be Russian and Western socioeconomic systems. IMT literature claims to utilize the reciprocity, redistribution, and exchange model of Karl Polanyi (1944, 1957). However, IMT suffers from a number of assumptive and methodological problems in its application, the first of which consists of the complete exclusion of reciprocity from consideration. The first section of the article is an explanation of problems with IMT, and the second section demonstrates some particulars of the IMT problems with a real-world social fabric matrix from a Western nation.
Economics
Keywords: Russia; economic policy; economics; institutional economics; institutional matrices theory; social fabric matrix; socioeconomics

The Belief in Economic Determinism, Neoliberalism, and the Significance of Polanyi's Contribution in the Twenty-First Century - Thomasberger, Claus (International Journal of Political Economy, 2012)
How can we explain why Karl Polanyi's book The Great Transformation is more relevant today than ever before? The central thesis of the paper is that Polanyi's analysis is groundbreaking because it goes far beyond the interpretation of the civilization of the nineteenth century. By focusing on the "belief of economic determinism," Polanyi challenges the juxtaposition of being and thinking, of material life-process and consciousness. He rejects the assumption that society encompasses a world of objective facts independent of theoretical beliefs and visions. Polanyi's work is of utmost importance today because by anticipating a change in approach such as the liberal authors made, from the opposite point of view, during the interwar period, he offers the key not only to the analysis of the market mechanism, but also to a critical understanding of neoliberalism.
Economics; Philosophy
Keywords: Austrian school; Austrian school of economics; Great Transformation; The (Book); Keynesian economics; Marxist philosophy; POLANYI; Karl; 1886-1964; belief & doubt - social aspects; central economic planning - social aspects; double movement; economic determinism; economic history - 19th century; economic planning; economic theory; fictitious commodities; free enterprise - social aspects; history of economics - 20th century; human behavior - economic aspects; laissez-faire; neoliberalism; neoliberalism - social aspects; self-fulfilling prophecy; socioeconomics; utopias - economic aspects